toner
By using a specific ratio of polydimethylsiloxane-treated silica fine particles on the surface of toner particles, the concentration of trimethylsilanol and ester groups is controlled, solving the problem of hydrocarbon wax leakage of toner in harsh environments and achieving stable image output for long-term use in high temperature and high humidity environments.
Patent Information
- Application Number
- CN202210462892.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-04-28
- Filing Date
- 2022-04-28
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2042-04-28
AI Technical Summary
When existing toners are stored in harsh environments with rapidly changing temperature and humidity, hydrocarbon wax seepage causes toner aggregates, affecting image quality. This is especially true when used for extended periods in high-temperature and high-humidity environments, resulting in vertical stripes and other undesirable image effects.
By using a specific proportion of polydimethylsiloxane to treat silica fine particles on the surface of colorant particles, the amount of trimethylsilanol and the ester group concentration distribution are controlled to form a shell with high heat resistance and high polarity, inhibiting hydrocarbon wax exudation and improving storage stability and durability.
Even after storage in harsh environments, and prolonged use in high temperature and high humidity environments, it can effectively inhibit the formation of toner aggregates, maintain image quality, and avoid vertical stripes and other adverse effects.
Smart Images

Figure CN115248539B_ABST
Abstract
Description
Technical Field
[0001] This disclosure relates to toners that can be used in electrophotographic image forming apparatus. Background Technology
[0002] Image forming equipment using electrophotographic technology, such as copiers and printers, requires smaller size, higher speed, higher image quality, and greater stability. To achieve compact devices, for example, fixing components such as rollers and films used to fix toner to recording media such as paper have been simplified and miniaturized. However, with the simplification and miniaturization of fixing components such as rollers and films, it becomes difficult to adequately heat and pressurize the toner in the fixing roller gap, preventing the release agent within the toner from fully leaching out, and causing the toner to adhere to the fixing film (hereinafter referred to as low-temperature contamination). To address these adverse effects, toners in which the toner particles include hydrocarbon waxes as a release agent have been proposed.
[0003] In addition to these requirements, toners are also required to have storage stability unaffected by harsh environments during transportation from manufacturing to consumer use. However, when toners containing hydrocarbon waxes within their particles are stored in harsh environments with rapidly changing temperature and humidity, the hydrocarbon waxes within the particles can leach to the surface of the particles. This leachable hydrocarbon wax increases the adhesion of the toner and forms toner aggregates.
[0004] In the case of single-component developers, toner aggregates are formed and remain in the frictional area between the toner carrier and the charge-imparting components, thereby adversely affecting the image (vertical stripes in halftone images). In particular, when toners are stored in harsh environments with rapidly changing temperature and humidity, followed by prolonged use in high-temperature and high-humidity environments, the size of toner aggregates formed by hydrocarbon wax exudation increases, and their adverse effects on the image become significant. In other words, conventional toners containing hydrocarbon waxes are required to have improved storage stability and durability, so that they are not easily affected even after prolonged image output in high-temperature and high-humidity environments following storage in harsh environments.
[0005] Therefore, as a means to further improve the storage stability and durability of toners containing hydrocarbon waxes, toners with added silica fine particles coated with highly hydrophobic silicone oil, and toners wherein a shell with excellent heat resistance is provided on the surface of the toner particles have been studied.
[0006] Japanese Patent Application Publication No. 2009-157161 discloses a toner in which fine silica particles hydrophobically modified with polydimethylsiloxane having a specific viscosity and modified side chains are added. Japanese Patent Application Publication No. 2017-044981 discloses a toner in which toner particles are coated with a heat-resistant, highly polar, amorphous polyester resin, and fine silica particles hydrophobically modified with polydimethylsiloxane are added. Summary of the Invention
[0007] The problem the invention aims to solve
[0008] As a result of the inventors' research, it was found that in the toner described in Japanese Patent Application Publication No. 2009-157161, adding fine silica particles hydrophobically modified with highly hydrophobic polydimethylsiloxane to the toner particles increases the toner's fluidity and improves its durability in high-temperature and high-humidity environments. However, it was discovered that when the toner is stored in a harsh environment with rapidly changing temperature and humidity, toner aggregates, presumably caused by the exudation of hydrocarbon waxes, are formed, adversely affecting the image. In other words, there is room for improvement in storage stability under harsh environments with rapidly changing temperature and humidity.
[0009] In the toner described in Japanese Patent Application Publication No. 2017-044981, the toner particles are coated with a heat-resistant, highly polar, amorphous polyester resin. Furthermore, it is believed that by adding fine silica particles treated with highly hydrophobic polydimethylsiloxane to the toner, its flowability and charge-carrying capacity in high-temperature and high-humidity environments are improved, while simultaneously suppressing the exudation of hydrocarbon waxes within the toner particles.
[0010] However, it has been found that when toners are stored in harsh environments with rapidly changing temperature and humidity, as described in Japanese Patent Application Publication No. 2009-157161, toner aggregates are produced, presumably due to the exudation of hydrocarbon waxes, which adversely affect the images.
[0011] This disclosure provides a toner that makes it unlikely that adverse effects on the image caused by toner aggregates will occur, even when the image is output for a long time in a high temperature and high humidity environment after being stored in a harsh environment.
[0012] A toner comprising:
[0013] Toner particles containing binder resins and hydrocarbon waxes; and
[0014] Inorganic fine particles, among which
[0015] The colorant includes fine silica particles surface-treated with polydimethylsiloxane represented by formula (A) and polydimethylsiloxane represented by formula (B) as inorganic fine particles;
[0016] In the analysis of volatile organic compounds of fine silica particles by headspace analysis at a heating temperature of 150°C, the total amount of trimethylsilanol, converted to octamethyltrisiloxane, was 1.0 to 5.0 ppm based on the mass of the fine silica particles.
[0017] In measurements of toner particles at a depth of 100 nm from the surface of the toner particles using time-of-flight secondary ion mass spectrometry, when the value obtained by dividing the amount of ions represented by the structure below (C) by the total number of counted ions is used as the standard value,
[0018] More than one peak of the standard value exists within 100 nm of the surface of the toner particles;
[0019]
[0020] When the maximum value among more than one peak of the standard value is represented by A(dmax), and the standard value on the surface of the toner particles is represented by A(0),
[0021] A(dmax) and A(0) satisfy the following equations (1) and (2):
[0022] 1.05≤A(dmax) / A(0)≤5.00 (1)
[0023] A(0)≥0.010 (2)
[0024]
[0025] In equation (B), R 1 It can be a methanol group, hydroxyl group, epoxy group, carboxyl group, alkyl group, or hydrogen atom, and R 2 The group is a methanol group, a hydroxyl group, an epoxy group, a carboxyl group, or a hydrogen atom; n and m are the average number of repeating units, n is 30 to 200, and m is 30 to 200; and each methyl group (-CH3) in the side chain of formula (B) can be replaced by a methanol group, a hydroxyl group, an epoxy group, a carboxyl group, or a hydrogen atom.
[0026] This disclosure provides a toner that makes it less likely to cause adverse effects on the image due to toner aggregates, even after prolonged output in a high-temperature and high-humidity environment following storage in harsh conditions. Further features of the invention will become apparent from the following description of exemplary embodiments with reference to the accompanying drawings. Attached Figure Description
[0027] Figure 1A time graph of the thermal cycle; and
[0028] Figure 2 This is a schematic diagram of the analytical results of time-of-flight secondary ion mass spectrometry analysis of toners. Detailed Implementation
[0029] Unless otherwise stated, expressions indicating a range of values, such as "from XX to YY" or "XX to YY", refer to a range of values that includes both the lower and upper limits as endpoints. When describing a range of values in segments, the upper and lower limits of each range can be combined arbitrarily.
[0030] The inventors have conducted in-depth research on toners including hydrocarbon waxes, which can provide images with excellent appearance even when outputting images for a long time in a high temperature and high humidity environment after being stored in harsh environments.
[0031] Conventional methods for improving the storage stability and durability of toners, including those containing hydrocarbon waxes, include studying toners that form a highly heat-resistant and highly polar shell on the surface of the toner particles, or adding hydrophobic silica fine particles to the surface of the toner particles. By providing a highly heat-resistant and highly polar shell on the surface of the toner particles, the leakage of hydrocarbon waxes located within the toner particles due to polarity differences can be suppressed, thereby improving storage stability. Furthermore, by adding hydrophobic silica fine particles to the surface of the toner particles, the decrease in toner flowability during prolonged use in high-temperature and high-humidity environments can be suppressed, thereby improving durability.
[0032] However, considering storage stability in harsh environments with rapid temperature and humidity changes, and durability after storage in harsh environments, the thermally induced activity of the hydrocarbon wax contained within the toner particles is higher than that of the binder resin, etc., and the hydrocarbon wax may seep to the surface of the toner particles when heated or cooled. In particular, since polydimethylsiloxane and hydrocarbon wax on the surface of silica fine particles may be compatible with each other, hydrocarbon wax may seep to the surface of the toner particles. As a result, the adhesion of the toner increases, and toner aggregates may be formed. For example, in the case of a single-component developer, the formed toner aggregates remain in the contact area between the toner carrier and the charging component. As a result, the toner is not sufficiently charged, the concentration is reduced, fogging occurs in non-image areas during toner development, or vertical stripes appear in halftone images.
[0033] Japanese Patent Application Publication No. 2009-157161 discloses a toner in which fine silica particles hydrophobically modified with polydimethylsiloxane using hydroxyl or phenyl-modified side chains are added. In the silica particles described in Japanese Patent Application Publication No. 2009-157161, due to the presence of functional groups in the side chains of the polydimethylsiloxane, the reactivity with silica is high, and the amount of polydimethylsiloxane transferred to the surface of the toner particles is reduced. Therefore, the increase in toner adhesion and the decrease in toner flowability can be suppressed.
[0034] However, because the toner has a vinyl resin surface and its polarity is lower than that of polyester resins, the toner may be compatible with polydimethylsiloxane on the surface of fine silica particles, and the shell's ability to mask hydrocarbon waxes is reduced. As a result, when the toner is stored in harsh environments, the exudation of hydrocarbon waxes cannot be suppressed, and toner aggregates are formed. Therefore, when the toner is stored in harsh environments and then used for extended periods in high-temperature and high-humidity environments, the image is adversely affected by these toner aggregates.
[0035] Meanwhile, Japanese Patent Application Publication No. 2017-044981 discloses a toner in which a shell of a heat-resistant, highly polar, amorphous polyester resin exists on the surface of the toner particles, and it has fine silica particles hydrophobically modified with polydimethylsiloxane, for example, represented by formula (A). However, it has been found that even with the use of such toners, the image can be adversely affected by toner aggregates.
[0036] The inventors considered the following reasons for the adverse effects on the image. First, in the polydimethylsiloxane hydrophobically treated silica fine particles represented by formula (A), a portion of the polydimethylsiloxane reacts with the silica matrix during surface treatment and adheres to the silica fine particles. The inventors believe that when the polydimethylsiloxane represented by formula (A) reacts with the silica matrix, the trimethylsilyl group at the end of the polydimethylsiloxane is eliminated, and the end is converted to a silanol group, which then reacts with the silica matrix. Therefore, the polydimethylsiloxane hydrophobically treated silica fine particles represented by formula (A) include trimethylsilanol as a byproduct.
[0037] Next, trimethylsilanol is a basic and polar substance. Therefore, trimethylsilanol tends to readily compatibility with the highly polar toner particle surface due to electrostatic interactions. Furthermore, since the polydimethylsiloxane and trimethylsilanol contained in the silica fine particles both contain trimethylsilyl groups, they tend to be compatible with each other. As a result, when the amount of trimethylsilanol in the silica fine particles increases, trimethylsilanol acts as a bridge between the polydimethylsiloxane in the silica fine particles and the highly polar toner particle surface. Consequently, a portion of the polydimethylsiloxane represented by formula (A) in the silica fine particles and the highly polar shell may become compatible with each other. Since the shell on the toner surface is compatible with a portion of the hydrophobic polydimethylsiloxane, the shell's masking effect on hydrocarbon waxes is reduced.
[0038] When toners are stored in harsh environments with rapidly changing temperature and humidity after their opacity against hydrocarbon waxes decreases, the hydrocarbon waxes contained within the toner particles may leach out. As a result, the hydrocarbon waxes leach to the toner surface, increasing the toner's adhesion and potentially causing toner aggregates. Furthermore, the inventors believe that when toners are used for extended periods in high-temperature and high-humidity environments, vertical stripes may appear in halftone images due to the toner aggregates formed during storage in harsh conditions.
[0039] As a result of the inventors’ in-depth research, it was discovered that, due to the following configuration, toners including hydrocarbon waxes can provide high-quality images even when outputting images for extended periods in high-temperature and high-humidity environments after storage in harsh environments.
[0040] That is, this disclosure relates to a toner comprising:
[0041] Toner particles containing binder resins and hydrocarbon waxes; and
[0042] Inorganic fine particles, among which
[0043] The colorant includes fine silica particles surface-treated with polydimethylsiloxane represented by formula (A) and polydimethylsiloxane represented by formula (B) as inorganic fine particles;
[0044] In the analysis of volatile organic compounds of fine silica particles by headspace analysis at a heating temperature of 150°C, the total amount of trimethylsilanol, converted to octamethyltrisiloxane, was 1.0 to 5.0 ppm based on the mass of the fine silica particles.
[0045] In the measurement of toner particles at a depth of 100 nm from the surface of the toner particles using time-of-flight secondary ion mass spectrometry, when the value obtained by dividing the amount of ions represented by the following formula (C) by the total number of counted ions is used as the standard value,
[0046] More than one peak of the standard value exists within 100 nm of the surface of the toner particles;
[0047]
[0048] When the maximum value among more than one peak of the standard value is represented by A(dmax), and the standard value on the surface of the toner particles is represented by A(0),
[0049] A(dmax) and A(0) satisfy the following equations (1) and (2):
[0050] 1.05≤A(dmax) / A(0)≤5.00 (1)
[0051] A(0)≥0.010 (2)
[0052]
[0053] In equation (B), R 1 It can be a methanol group, hydroxyl group, epoxy group, carboxyl group, alkyl group, or hydrogen atom, and R 2 The group is a methanol group, a hydroxyl group, an epoxy group, a carboxyl group, or a hydrogen atom; n and m are the average number of repeating units, n is 30 to 200, and m is 30 to 200; and each methyl group (-CH3) in the side chain of formula (B) can be replaced by a methanol group, a hydroxyl group, an epoxy group, a carboxyl group, or a hydrogen atom.
[0054] The following discussion explains why the aforementioned properties are achieved by treating silica fine particles with polydimethylsiloxane represented by formulas (A) and (B) and by controlling the amount of trimethylsilanol in the silica fine particles and the distribution of ester group concentration near the toner surface. The inventors have found that for toners comprising hydrocarbon waxes, the following points are important for suppressing the leaching of hydrocarbon waxes during storage in harsh environments and for suppressing adverse effects on images during prolonged use in high-temperature and high-humidity environments after storage in harsh environments.
[0055] (1-1) The amount of trimethylsilanol in the silica fine particles including polydimethylsiloxane is small, and the surface of the toner particles is unlikely to be compatible with the polydimethylsiloxane contained in the silica fine particles.
[0056] (1-2) A portion of the ester group concentration at positions higher than the surface of the toner particles and at a depth of 100 nm from the surface of the toner particles exists in the region near the surface of the toner particles within a depth of 100 nm from the surface of the toner particles. That is, the following standard values of the ionic fragments of the ester group have more than one peak, and the exudation of hydrocarbon waxes within the toner is suppressed.
[0057] The above (1-1) is strongly influenced by the composition of the polydimethylsiloxane used as a surface treatment agent for silica fine particles and the resin composition on the surface of the toner particles. The low amount of trimethylsilanol contained in the silica fine particles and the low compatibility of the polydimethylsiloxane in the silica fine particles with the surface of the toner particles allow for suppression of the exudation of hydrocarbon waxes within the toner particles when stored in harsh environments. Therefore, toner aggregates are unlikely to occur even after prolonged image output in high temperature and high humidity environments following storage in harsh environments.
[0058] Meanwhile, the above (1-2) is strongly influenced by the resin composition and orientation state near the surface of the toner particles. As a result of the standard value of ester group ion fragments having more than one peak near the surface of the toner particles, the leakage of hydrocarbon waxes located within the toner particles due to polarity differences can be suppressed when stored in harsh environments. In addition, the presence of a peak means that the ester group concentration on the surface of the toner particles is lower than the ester group concentration in the region within the toner particles 100 nm away from the surface of the toner particles. Therefore, it is expected to reduce the possibility of compatibility between the polydimethylsiloxane of the silica fine particles described in (1-1) and the surface of the toner particles. Therefore, even when images are output for a long time in a high temperature and high humidity environment after storage in a harsh environment, toner aggregates are unlikely to occur.
[0059] As described above, by satisfying (1-1) and (1-2), even when the image is output for a long time in a high temperature and high humidity environment after being stored in a harsh environment, the adverse effects on the image caused by toner aggregates can be suppressed for the first time.
[0060] Specifically, to make the surface of the toner unlikely to be compatible with the fine silica particles, the inorganic fine particles include silica fine particles surface-treated with polydimethylsiloxane represented by formula (A) and polydimethylsiloxane represented by formula (B). For example, it is assumed that as a result of surface-treating the silica fine particles with polydimethylsiloxane, the polydimethylsiloxane binds to the silica fine particles and / or the polydimethylsiloxane is physically adsorbed onto the silica fine particles.
[0061] Because the silica fine particles are treated with the two polydimethylsiloxanes mentioned above, the immobilization rate of polydimethylsiloxane remains higher than that of silica fine particles treated with polydimethylsiloxane represented by formula (A) alone, while the amount of trimethylsilanol in the silica fine particles can be reduced. This is believed to be because the polydimethylsiloxane represented by formula (B) has high reactivity with silica fine particles. This can reduce the possibility of compatibility between the polydimethylsiloxane in the silica fine particles and the surface of the toner particles.
[0062] Furthermore, the polydimethylsiloxane represented by formula (A) lacks reactive functional groups and therefore has lower polarity than the polydimethylsiloxane represented by formula (B), making it less likely to be compatible with the highly polar surface of toner particles. Therefore, by using a combination of the polydimethylsiloxane represented by formula (A) and the polydimethylsiloxane represented by formula (B), the formation of trimethylsilanol can be suppressed, and the polarity of the polydimethylsiloxane itself within the silica fine particles can be reduced. This reduces the likelihood of compatibility between the polydimethylsiloxane in the silica fine particles and the highly polar surface of toner particles.
[0063] Since the polydimethylsiloxane in the fine silica particles is unlikely to be compatible with the surface of the toner particles, the masking effect of the toner particle surface on hydrocarbon waxes can be maintained. As a result, hydrocarbon waxes present within the toner particles are also unlikely to leach out, making it unlikely that toner aggregates will form even when stored in harsh environments.
[0064] Furthermore, in the analysis of volatile organic compounds from fine silica particles by headspace analysis at a heating temperature of 150°C, the total amount of trimethylsilanol, converted from octamethyltrisiloxane, needs to be between 1.0 and 5.0 ppm based on the mass of the fine silica particles.
[0065] The amount of trimethylsilanol in the silica fine particles within the above range refers to a low amount of trimethylsilanol separated from the polydimethylsiloxane contained in the silica fine particles. Therefore, by controlling the amount of trimethylsilanol in the silica fine particles within the above range, the polarity of the polydimethylsiloxane can be reduced, and the possibility of compatibility between the polydimethylsiloxane and the toner particle surface can be reduced. Therefore, even when stored in harsh environments, the hydrocarbon wax within the toner particles is less likely to leach out, and toner aggregates are less likely to form. As a result, even when the toner is used for extended periods in high-temperature and high-humidity environments after storage in harsh environments, adverse effects on the image caused by toner aggregates can be suppressed.
[0066] In the fine silica particles, the total amount of trimethylsilanol, converted from octamethyltrisiloxane, is preferably from 1.1 ppm to 3.0 ppm, and more preferably from 1.2 ppm to 2.5 ppm, based on the mass of the fine silica particles. The total amount of trimethylsilanol in the fine silica particles can be controlled by the type of treatment agent used to hydrophobize the surface of the fine silica particles, the amount of the treatment agent, and the particle size of the fine silica particles.
[0067] When the total amount of trimethylsilanol in the silica fine particles is less than 1.0 ppm, this indicates that the amount treated with polydimethylsiloxane is too small, or that the polydimethylsiloxane in the silica fine particles is the polydimethylsiloxane represented by formula (B). Since the polydimethylsiloxane represented by formula (B) has reactive functional groups at the ends or in the side chains, it has high reactivity with the silica matrix, and the amount of polydimethylsiloxane transferred is reduced when the silica fine particles come into contact with various components. Here, as a result of a portion of the polydimethylsiloxane transferring from the toner to the various components upon contact, the polydimethylsiloxane contained in the silica fine particles reduces the adhesion between the toner and the various components.
[0068] However, if the amount of polydimethylsiloxane used is too small, or if only the highly reactive polydimethylsiloxane represented by formula (B) is used, the amount of polydimethylsiloxane transferred when the silica fine particles come into contact with various components is reduced. Therefore, the adhesion between the toner and the various components increases. As a result, toner aggregates may form when the toner is used for extended periods in high temperature and humidity environments after storage in harsh environments. In the case of single-component developers, the resulting toner aggregates remain in the frictional area between the toner-carrying component and the charged component, thereby adversely affecting the image (vertical stripes in halftone images).
[0069] Furthermore, when the total amount of trimethylsilanol in the silica fine particles exceeds 5.0 ppm, the polydimethylsiloxane in the silica fine particles becomes polar, making the polydimethylsiloxane and the surface of the toner particles potentially compatible with each other. As a result, due to the polarity of the toner particle surface, the masking effect that inhibits the exudation of hydrocarbon waxes located within the toner is reduced, and hydrocarbon waxes located within the toner particles may exudate when stored in harsh environments.
[0070] When the standard value is obtained by dividing the amount of ions of the structure represented by the following formula (C) measured from the surface of the toner particle to a depth of 100 nm by time-of-flight secondary ion mass spectrometry by the total number of counted ions, there must be more than one peak of the standard value within a range of 100 nm from the surface of the toner particle. The maximum value among the more than one peak of the standard value is represented by A(dmax) and the standard value on the surface of the toner particle (i.e., at a depth of 0 nm) is represented by A(0), then the following formulas (1) and (2) are satisfied.
[0071] 1.05≤A(dmax) / A(0)≤5.00 (1)
[0072] A(0)≥0.010 (2)
[0073]
[0074] By controlling the expression to satisfy Equation (1) near the surface of the toner particles (in the region up to 100 nm from the surface of the toner particles), it can be ensured that a certain amount of ester groups are present inside the toner particles relative to their surface. That is, this means that the high polarity polyester resin is present in a greater amount than on the surface of the toner particles slightly inside the toner particles, and the exudation of hydrocarbon waxes within the toner is suppressed even when stored in harsh environments.
[0075] Furthermore, Equation (2) indicates that the ester concentration on the surface (depth 0m) of the toner particles is above a certain level. As a result of controlling the toner to satisfy Equation (1) and also ensuring that the ester concentration near the surface of the toner particles satisfies Equation (2), the peak of the ester concentration exists near the surface of the toner particles, and the peak size can be kept above a certain level while reducing the ester concentration present on the surface of the toner particles.
[0076] By reducing the concentration of ester groups present on the surface of toner particles, the likelihood of compatibility between the silica particles and the toner particle surfaces can be reduced, even when the silica particles include trimethylsilanol. Furthermore, when the peak concentration of ester groups near the toner particle surface exceeds a certain level, the polarity difference between the toner particle surface and the hydrocarbon wax increases, and the exudation of hydrocarbon waxes within the toner to the toner particle surface can be suppressed. As a result, even after prolonged use of the toner in high-temperature and high-humidity environments following storage in harsh conditions, adverse effects on images caused by toner aggregates can be suppressed.
[0077] The ratio A(dmax) / A(0) expressed by formula (1) is preferably from 1.08 to 2.00, and more preferably from 1.15 to 1.50. When A(dmax) / A(0) is less than 1.05, it means that the ester concentration at a depth of 0 to 100 nm is not much higher than the ester concentration on the surface of the toner particles. Therefore, when stored in harsh environments, the exudation of hydrocarbon waxes within the toner cannot be suppressed, and toner aggregates may occur.
[0078] Furthermore, when A(dmax) / A(0) is greater than 5.00, it indicates that the ester groups are excessively and unevenly distributed in the resin relative to the inner surface of the toner particles. To achieve this range, resins with extremely high or low physical properties, such as molecular weight and acid value, are required, and the concentration of ester groups in the toner particles can vary greatly. As a result, when stored in harsh environments, toner aggregates may occur due to the inability to suppress the exudation of hydrocarbon waxes within the toner. A(dmax) / A(0) can be controlled by the high-temperature, high-pH treatment step described later and the composition of the polar resin on the surface of the toner particles.
[0079] Regarding formula (2), in a toner containing polyester resin within a depth of 100 nm from the surface of the toner particles and satisfying formula (1), a certain amount of the structure represented by formula (C) can exist on the surface of the toner particles (depth 0 nm). Therefore, it is considered difficult to produce toners with A(0) less than 0.010.
[0080] A(0) is preferably 0.020 or higher, more preferably 0.030 or higher, and even more preferably 0.040 or higher. There is no particular limit to the upper limit, but it is preferably 0.100 or lower, more preferably 0.080 or lower, and even more preferably 0.074 or lower. A(0) can be controlled by the high temperature and high pH treatment step described later and the composition of the polar resin on the surface of the toner particles.
[0081] A(dmax) is preferably 0.040 or higher, and more preferably 0.050 or higher. There is no particular limit to the upper limit, but it is preferably 0.200 or lower, more preferably 0.120 or lower, and even more preferably 0.100 or lower.
[0082] When the standard value is obtained by dividing the amount of ions of the structure represented by equation (C) measured from the surface of the toner particle to a depth of 100 nm using time-of-flight secondary ion mass spectrometry by the total number of counted ions, and the standard value at a depth of 100 nm from the surface of the toner particle is represented by A(100), the following equation (3) is satisfied.
[0083] 1.05≤A(dmax) / A(100)≤5.00 (3)
[0084] Satisfying equation (3) means that the ester concentration in the region closer to the surface of the toner particles is higher than the ester concentration at a depth of 100 nm from the surface of the toner particles. That is, the ester concentration of the resin in the region where hydrocarbon wax exists within the toner particles is higher than a certain value. As a result of the ester concentration near the surface of the toner particles being higher than the ester concentration inside the toner particles, hydrocarbon wax located inside the toner particles tends to remain inside the toner particles due to the difference in polarity.
[0085] Therefore, the leakage of hydrocarbon waxes located within the toner particles to the toner surface can be suppressed. As a result, even when the toner is used for a long time in a high-temperature and high-humidity environment after being stored in a harsh environment, the adverse effects on the image caused by toner aggregates can be suppressed. A(dmax) / A(100) is more preferably 1.10 or more, and even more preferably 1.20 or more. At the same time, the upper limit is more preferably 3.00 or less, and even more preferably 2.00 or less.
[0086] The ratio A(dmax) / A(100) can be controlled by the high-temperature, high-pH treatment step described later and the composition of the polar resin on the surface of the toner particles. A(100) is preferably 0.030 or more, and more preferably 0.040 or more. There is no particular limit to the upper limit, but it is preferably 0.200 or less, more preferably 0.100 or less, and even more preferably 0.080 or less.
[0087] The inventors believe that, according to the following mechanism, the ester groups represented by formula (C) above can be unevenly distributed near the surface of the toner particles. This can be controlled by creating a design that also considers the presence of the structure represented by formula (C) in order to obtain, for example, a specific compositional distribution in which monomer units having nonpolar groups and monomer units having polar groups are unevenly distributed in the polyester molecule.
[0088] As a specific method, the distribution of ester bond segments in the polyester resin can be controlled by the orientation state of the carboxylic acid groups at the ends of the polyester resin, which is a polar resin, near the surface of the toner particles, or by using a combination of polymers with significantly different polarity distributions. Furthermore, for example, when toner particles comprising a polyester resin having a structure represented by formula (C) are treated in an aqueous medium with a pH and heat level above a certain level, the ester bond segments in the polyester resin may migrate to the surface of the toner particles. Simultaneously, it is believed that since the polyester resin comprising the structure represented by formula (C) has a distribution of ester bond segments, this distribution also occurs in the orientation state, and the structure represented by formula (C) can be non-uniformly distributed in a region within 100 nm of the toner particle surface.
[0089] <fine silica particles>
[0090] The following describes the fine silica particles. As described above, the fine silica particles are surface-treated with polydimethylsiloxanes represented by formulas (A) and (B). Furthermore, the fine silica particles are preferably surface-treated with polydimethylsiloxanes represented by formula (A) and (D). That is, the polydimethylsiloxane represented by formula (B) is preferably the polydimethylsiloxane represented by formula (D).
[0091]
[0092] In the formula, R 1 It is a methanol-based, hydroxyl-based, epoxy-based, carboxyl-based, alkyl group (preferably having 1 to 6 carbon atoms, and more preferably 1 to 3 carbon atoms), or a hydrogen atom, and R 2 It can be a methanol group, hydroxyl group, epoxy group, carboxyl group, or hydrogen atom. Preferably, R 1 and R 2Each is a methanol group, a hydroxyl group, or a hydrogen atom. The methyl groups in the side chains of formula (B) may be substituted with methanol groups, hydroxyl groups, epoxy groups, carboxyl groups, or hydrogen atoms. n, m, and p are the average number of repeating units, where n is 30 to 200 (preferably 40 to 100, and more preferably 50 to 80), m is 30 to 200 (preferably 40 to 100, and more preferably 50 to 80), and p is 30 to 200 (preferably 40 to 100, and more preferably 50 to 80).
[0093] Treating silica fine particles with two polydimethylsiloxanes of formula (A) and (D) reduces the amount of trimethylsilanol in the silica fine particles compared to treating silica fine particles with polydimethylsiloxanes represented by formula (A) and (B). This is due to the high reactivity of the polydimethylsiloxane represented by formula (D) with the silica matrix. Therefore, the silica fine particles and the polydimethylsiloxane on the surface of the toner are unlikely to be compatible with each other. As a result, toner aggregates are unlikely to occur even after prolonged use in a high-temperature and high-humidity environment following storage in harsh environments.
[0094] The number average particle size of the primary particles of the silica fine particles is preferably 5 nm to 30 nm, and more preferably 6 nm to 12 nm. By controlling the number average particle size of the primary particles of the silica fine particles within the above range, the flowability of the toner can be significantly improved when silica fine particles are added. As a result, even when the toner is used for a long time in a high temperature and high humidity environment after being stored in a harsh environment, the adverse effects on the image caused by toner aggregates can be suppressed.
[0095] Examples of fine silica particles include dry silica, known as fumed silica, produced by the gas-phase oxidation of silicon halides, and wet silica produced from water glass, etc. Dry silica with few silanol groups on its surface and interior and without production residues is preferred.
[0096] The polydimethylsiloxanes represented by formulas (A), (B), and (D) are preferably highly volatile, allowing them to be effectively evaporated and removed by surface treatments described later. Therefore, the polydimethylsiloxanes preferably have relatively small molecular weights.
[0097] The molecular weight of the polydimethylsiloxane represented by formulas (A), (B), and (D), as a number-average molecular weight, is preferably 250 to 50,000, more preferably 250 to 10,000, and even more preferably 250 to 5,000. When the molecular weight of the polydimethylsiloxane is 50,000 or less, its volatility is appropriate, and the polydimethylsiloxane is easily evaporated and removed by the surface treatment described later, so that it can easily react with the silica-based material. At the same time, when the molecular weight of the polydimethylsiloxane is 250 or more, it becomes easier to impart high hydrophobicity.
[0098] From the viewpoint of uniform treatment, it is preferred that the polydimethylsiloxane represented by formulas (A), (B), and (D) be used for surface treatment after being diluted with a suitable solvent to, for example, about 5% to 50% by mass. Examples of solvents include hexane, toluene, alcohols (e.g., aliphatic alcohols having 1 to 8 carbon atoms such as methanol, ethanol, and propanol), and acetone, water, or mixtures of two or more thereof.
[0099] The amount of polydimethylsiloxane used for surface treatment of silica fine particles varies depending on the type of silica base material (specific surface area, etc.) and the type of polydimethylsiloxane (molecular weight, etc.), and is not particularly limited. Generally, the amount of polydimethylsiloxane relative to 100 parts by weight of silica fine particles is preferably 1 to 40 parts by weight, more preferably 2 to 35 parts by weight, and even more preferably 5 to 30 parts by weight. When the amount of polydimethylsiloxane used is above the lower limit, sufficient surface treatment can be performed, and silica fine particles with high hydrophobicity can be obtained. Meanwhile, when polydimethylsiloxane is used below the upper limit, the hydrophobicity of the silica fine particles can be improved, and aggregation is less likely to occur.
[0100] The amount of polydimethylsiloxane represented by formula (A) used for surface treatment is preferably 3 to 40 parts by mass, more preferably 5 to 35 parts by mass, and even more preferably 10 to 30 parts by mass, relative to 100 parts by mass of fine silica particles before surface treatment. The amount of polydimethylsiloxane represented by formula (B) used for surface treatment is preferably 1 to 35 parts by mass, more preferably 2 to 30 parts by mass, and even more preferably 5 to 20 parts by mass, relative to 100 parts by mass of fine silica particles before surface treatment.
[0101] In the surface treatment, the mass ratio (B) / (A) of polydimethylsiloxane represented by formula (B) to polydimethylsiloxane represented by formula (A) is preferably 0.05 to 10.00, more preferably 0.06 to 6.00, and even more preferably 0.20 to 1.00.
[0102] (Surface treatment method)
[0103] The surface treatment method is preferably carried out in an inert gas atmosphere, such as nitrogen, to prevent hydrolysis and oxidation. Specifically, it can be carried out in a method in which a silica-based material is placed in a container equipped with a stirring device such as a Henschel mixer and stirred under nitrogen purging, and a diluted solution of polydimethylsiloxane is sprayed and mixed with the silica material, followed by heating and reaction. Spraying can be carried out before heating, or it can be carried out simultaneously with heating to or below the treatment temperature.
[0104] (Processing conditions)
[0105] In the surface treatment, the predetermined amount of polydimethylsiloxane is applied to a silica-based material and heated under stirring to allow the polydimethylsiloxane to react and immobilize on the surface of the silica-based material. Here, the polydimethylsiloxane can be diluted with the various solvents described above and then applied to the silica-based material.
[0106] The heating temperature in this surface treatment varies depending on the reactivity of the polydimethylsiloxane used, but is preferably from 150°C to 380°C, and more preferably from 250°C to 350°C. The treatment time varies depending on the heating temperature and the reactivity of the polydimethylsiloxane used, but is preferably from 5 minutes to 300 minutes, more preferably from 50 minutes to 200 minutes, and even more preferably from 80 minutes to 160 minutes.
[0107] Under the aforementioned treatment temperature and time, polydimethylsiloxane can react fully with the silica base material, and the hydrophobicity of the fine silica particles is improved. Furthermore, production efficiency is also improved.
[0108] Preferably, the silica base material is hydrophobically treated using a polydimethylsiloxane represented by formula (A), which has excellent hydrophobicity-enhancing properties, and then the silica fine particles are treated with a polydimethylsiloxane represented by formula (B) or (D). By treating in the above sequence, the amount of residual trimethylsilanol in the silica fine particles can be reduced, and silica fine particles with high hydrophobicity can be obtained.
[0109] From the viewpoint of improving flowability and electrical conductivity, the amount of silica fine particles relative to 100 parts by weight of toner particles is preferably 0.1 to 4.0 parts by weight, more preferably 0.2 to 3.5 parts by weight, and even more preferably 0.7 to 1.5 parts by weight. The toner may have inorganic fine particles other than the aforementioned silica fine particles on the surface of the toner particles. Examples of inorganic fine particles include titanium dioxide particles, aluminum oxide particles, and particles of their oxides.
[0110] <Adhesive Resin>
[0111] The toner particles include a binder resin. There are no particular limitations on the binder resin, and known binder resins can be used. For example, the following resins may be mentioned: vinyl resins, polyester resins, polyol resins, polyvinyl chloride resins, phenolic resins, phenolic resins modified with natural resins, maleic acid resins modified with natural resins, acrylic resins, methacrylic resins, polyvinyl acetate, silicone resins, polyurethane resins, polyamide resins, furan resins, epoxy resins, xylene resins, polyvinyl butyral, terpene resins, coumarone indene resins, and petroleum resins. Vinyl resins, polyester resins, and hybrid resins in which polyester resins and vinyl resins are mixed or partially reacted are preferred.
[0112] <Polyester Resin>
[0113] The adhesive resin preferably includes a polyester resin. Polyester resins will be described below. There are no particular limitations on the polyester resin, but amorphous polyester resins are preferred, and examples include the following.
[0114] Examples of dicarboxylic acid components include the following dicarboxylic acids or their derivatives: phthalic acid, terephthalic acid, isophthalic acid, and phthalic anhydride, etc., or their anhydrides or lower alkyl esters; alkyl dicarboxylic acids, such as succinic acid, adipic acid, sebacic acid, and azelaic acid, etc., or their anhydrides or lower alkyl esters; alkenyl succinic acids or alkyl succinic acids, such as dodecenyl succinic acid and dodecyl succinic acid, or their anhydrides or lower alkyl esters; and unsaturated dicarboxylic acids, such as fumaric acid, maleic acid, citracic acid, and itaconic acid, or their anhydrides or lower alkyl esters.
[0115] Examples of diol components include the following: ethylene glycol, polyethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,6-hexanediol, neopentyl glycol, 1,4-cyclohexanediol (CHDM), hydrogenated bisphenol A, bisphenols and their derivatives.
[0116] In addition to the aforementioned dicarboxylic acid compounds and diol compounds, polyester resins may include monocarboxylic acid compounds, monool compounds, tri- or higher carboxylic acid compounds, and tri- or higher alcohol compounds as constituent components.
[0117] Examples of monocarboxylic acid compounds include aromatic carboxylic acids having 30 or fewer carbon atoms, such as benzoic acid and p-methylbenzoic acid; and aliphatic carboxylic acids having 30 or fewer carbon atoms, such as stearic acid and betaine acid. Examples of monohydric alcohol compounds include aromatic alcohols having 30 or fewer carbon atoms, such as benzyl alcohol; and aliphatic alcohols having 30 or fewer carbon atoms, such as lauryl alcohol, cetyl alcohol, stearyl alcohol, and betaine alcohol.
[0118] There are no particular restrictions on carboxylic acid compounds with three or more nucleotides, and examples include trimellitic acid, trimellitic anhydride, and pyromellitic acid. Examples of alcohol compounds with three or more nucleotides include trimethylolpropane, pentaerythritol, and glycerol.
[0119] The polyester resin preferably comprises monomer units represented by formula (E), monomer units represented by formula (F), and monomer units represented by formula (G). A monomer unit refers to the form in which the monomeric substances in the polymer react. The content of monomer units represented by formula (E) in the polyester resin is preferably 30% to 50% by mass, and more preferably 40% to 50% by mass. The content of monomer units represented by formula (F) in the polyester resin is preferably 25% to 50% by mass, and more preferably 30% to 45% by mass. The content of monomer units represented by formula (G) in the polyester resin is preferably 0.4% to 50% by mass, more preferably 1% to 30% by mass, and even more preferably 6% to 25% by mass.
[0120] In the formula, R 3 Representing the benzene ring, preferably bonded at the para position. Each R 4 Represents ethylene or propyleneene, where x and y are integers greater than or equal to 1, and the average value of x+y is between 2 and 10. R 5 It represents ethylene or propylene, and is preferably ethylene.
[0121]
[0122] The inventors believe that by controlling the content ratio of monomer units in the polyester resin within the aforementioned range, the concentration of ester groups in the polyester resin can be easily increased, and the orientation state of the carboxylic acid groups at the polymer terminals can be easily aligned. That is, since the polyester resin in which the content ratio of monomer units is controlled within the aforementioned range includes a certain amount of monomer units with low molecular weight represented by formula (G), the concentration of ester groups in the polyester resin can be increased. Furthermore, since it contains a certain amount of monomer units with low molecular weight represented by formula (G), the softness can be improved. The inventors believe that by increasing the concentration of ester groups in the polyester resin and improving the softness of the polyester resin, it becomes easier to align the orientation state of the carboxylic acid groups at the polymer terminals by using the polarity of the ester groups.
[0123] As a result, the concentration of ester groups near the surface of toner particles can be easily controlled within the range of formulas (1) and (2), and even when the toner is used for a long time in a high temperature and high humidity environment after being stored in a harsh environment, the adverse effects on the image caused by toner aggregates can be suppressed.
[0124] The polyester resin preferably comprises monomer units represented by the following formula (H).
[0125]
[0126] When a polyester resin includes monomer units obtained by polymerizing isosorbide represented by formula (H), the polarity of the polyester resin can be optimized, and monomer units with non-polar groups and monomer units with polar groups may be unevenly distributed in the polyester resin.
[0127] The inventors believe the reasons are as follows. Since the monomer unit represented by formula (H) has an ether bond in its cyclic structure, the influence on the polarity of the ester group component of each monomer unit can be appropriately mitigated compared to monomer units with ether bonds, such as ethylene glycol. Furthermore, since the monomer unit represented by formula (H) has a cyclic structure in which the oxygen atom faces outward, it becomes easier to achieve a non-uniform distribution of polar groups by using the polarity derived from the cyclic structure, compared to monomer units including alkyl chains in the main chain, such as ethylene glycol. The inventors believe this is why the polyester resin can be appropriately endowed with polarity caused by the ester group component, and why alcohol monomer units with polar groups represented by formulas (G) and (H) and alcohol monomer units with non-polar groups represented by formula (F) can be non-uniformly distributed. As a result, the concentration of ester groups near the surface of toner particles can be easily controlled within the range of formulas (1) and (2), and even when the toner is used for a long time in a high temperature and high humidity environment after being stored in a harsh environment, the adverse effects on the image caused by toner aggregates can be suppressed.
[0128] The content of monomer units represented by formula (H) in the polyester resin is preferably from 1.0% to 4.0% by mass, and more preferably from 2.0% to 3.5% by mass.
[0129] The weight-average molecular weight of the polyester resin is preferably from 6,000 to 20,000, and more preferably from 9,000 to 15,000. The acid value of the polyester resin is preferably from 3.0 mg KOH / g to 15.0 mg KOH / g, and more preferably from 4.0 mg KOH / g to 10.0 mg KOH / g. There are no particular limitations on the production method of the polyester resin, and known methods can be used.
[0130] (polymerizable monomers)
[0131] Adhesive resins may include vinyl-based resins. Vinyl-based monomers capable of free radical polymerization are used as polymerizable monomers for producing vinyl-based resins. Monofunctional or polyfunctional monomers may be used as vinyl-based monomers.
[0132] Monofunctional monomers include styrene; styrene derivatives such as α-methylstyrene, β-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, p-methoxystyrene, and p-phenylstyrene; acrylic polymeric monomers such as methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, dibutyl phosphate, ethyl acrylate, and 2-benzoyloxyethyl acrylate; methacrylic polymeric monomers such as methyl methacrylate, ethyl methacrylate, and dibutyl phosphate, ethyl methacrylate; methylene aliphatic monocarboxylic acid esters; vinyl esters such as vinyl acetate and vinyl propionate; vinyl ethers such as vinyl methyl ether, vinyl ethyl ether, and vinyl isobutyl ether; and vinyl ketones such as vinyl methyl ketone, vinyl hexyl ketone, and vinyl isopropyl ketone.
[0133] The polymerizable monomer preferably includes styrene or styrene derivatives and acrylic polymerizable monomers. That is, the adhesive resin preferably comprises a styrene-acrylic resin. The styrene-acrylic resin is a polymer comprising at least one monomer selected from the group consisting of styrene and styrene derivatives, and at least one monomer selected from the group consisting of acrylic polymerizable monomers and methacrylic polymerizable monomers. The styrene-acrylic resin is preferably a polymer comprising styrene and at least one monomer selected from the group consisting of acrylic polymerizable monomers and methacrylic polymerizable monomers.
[0134] Examples of multifunctional monomers include diethylene glycol diacrylate, triethylene glycol diacrylate, tetraethylene glycol diacrylate, polyethylene glycol diacrylate, tetramethylolpropane tetramethacrylate, divinylbenzene, and divinyl ether.
[0135] Crosslinking agents with polymerizable monomers can also be used. Specifically, compounds having two or more polymerizable double bonds can be used, such as carboxylic acid esters with two double bonds, such as propylene glycol diacrylate, ethylene glycol diacrylate, 1,6-hexanediol diacrylate, and 1,3-butanediol dimethacrylate; aromatic divinyl compounds such as divinylbenzene and divinylnaphthalene; divinyl compounds such as divinylaniline, divinyl ether, divinyl sulfide, and divinyl sulfone; and compounds having three or more vinyl groups. From the viewpoint of achieving both low-temperature fixing and high-temperature elasticity, carboxylic acid esters are preferred. These crosslinking agents can be used alone or in combination.
[0136] The amount of crosslinking agent added is preferably 0.01 to 5.00 parts by weight, and more preferably 0.10 to 3.00 parts by weight, relative to 100 parts by weight of the polymerizable monomer or adhesive resin used to produce the adhesive resin.
[0137] Polymerization initiators can also be used in the production of toner granules. Oil-soluble and / or water-soluble initiators are used as polymerization initiators. The half-life of the polymerization initiator at the reaction temperature during the polymerization reaction is preferably 0.5 hours to 30 hours. Furthermore, it is preferred that the polymerization reaction be carried out with an addition amount of polymerization initiator of 0.5 to 20 parts by mass relative to 100 parts by mass of polymerizable monomer, because polymers with a maximum molecular weight typically between 10,000 and 100,000 are obtained, and toner granules with suitable strength and melt properties can be obtained.
[0138] Examples of polymerization initiators include, for example, azo or diazo polymerization initiators such as 2,2'-azobis-(2,4-dimethylpentanonitrile), 2,2'-azobisisobutyronitrile, 1,1'-azobis(cyclohexane-1-carboxynitrile), 2,2'-azobis-4-methoxy-2,4-dimethylpentanonitrile, and azobisisobutyronitrile; and peroxide polymerization initiators such as benzoyl peroxide, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxyneoplate, tert-butyl peroxyisobutyrate, tert-butyl peroxyneodecanate, methyl ethyl ketone peroxide, diisopropyl peroxycarbonate, cumene hydroperoxide, 2,4-dichlorobenzoyl peroxide, and lauroyl peroxide; etc.
[0139] To control the degree of polymerization of polymerizable monomers, known chain transfer agents and polymerization inhibitors can be added and used.
[0140] Core-shell structure
[0141] The toner particles preferably have a core-shell structure, having a core particle and a shell on the surface of the core particle. Preferably, the core particle comprises a styrene-acrylic resin and the shell comprises a polyester resin. Because the toner particles have this core-shell structure, hydrocarbon waxes contained within the toner particles are less likely to leach to the surface of the toner particles. This is because hydrocarbon waxes have a higher affinity for the styrene-acrylic resin of the core particle than the polyester resin of the shell; therefore, even when stored in harsh environments, the hydrocarbon waxes within the toner may remain in the styrene-acrylic resin of the core particle. As a result, even when the toner is used for extended periods in high temperature and high humidity environments after storage in harsh environments, adverse effects on the image caused by toner aggregates can be suppressed.
[0142] In cross-sectional observation of the toner using a transmission electron microscope, the average shell thickness is preferably 100 nm to 200 nm, and more preferably 105 nm to 160 nm. When the shell thickness of the toner particles is within the above range, the polyester resin contained in the shell can further suppress the exudation of hydrocarbon waxes. As a result, even when the toner is used for a long time in a high temperature and high humidity environment after being stored in a harsh environment, the adverse effects on the image caused by toner aggregates can be suppressed.
[0143] Preferably, the colorant has the following composition.
[0144] A toner comprising:
[0145] Toner particles containing styrene-acrylic resins, polyester resins, and hydrocarbon waxes; and
[0146] Inorganic fine particles, among which
[0147] Inorganic fine particles include polydimethylsiloxane represented by formula (A) and silica fine particles surface-treated with polydimethylsiloxane represented by formula (B);
[0148] The toner particles consist of a core particle and a shell on the surface of the core particle;
[0149] The core particles include styrene-acrylic resins;
[0150] The shell includes polyester resin;
[0151] In cross-sectional observations of the toner using transmission electron microscopy, the average thickness of the shell was 100 to 200 nm.
[0152] In the measurement of toner particles from their surface to a depth of 100 nm using time-of-flight secondary ion mass spectrometry, when the value obtained by dividing the amount of ions represented by equation (C) by the total number of counted ions is used as the standard value,
[0153] More than one peak of the standard value exists within 100 nm of the surface of the toner particles;
[0154] When the maximum value among more than one peak of the standard value is represented by A(dmax), and the standard value on the surface of the toner particles is represented by A(0),
[0155] A(dmax) and A(0) satisfy the following equations (1) and (2):
[0156] 1.05≤A(dmax) / A(0)≤5.00 (1)
[0157] A(0)≥0.010 (2).
[0158] <hydrocarbon wax>
[0159] Hydrocarbon waxes are preferably aliphatic hydrocarbon waxes. Examples include low molecular weight polyethylene, low molecular weight polypropylene, microcrystalline wax, Fischer-Tropsch wax, paraffin wax, and polyolefin waxes. These waxes can be used alone or in combination of two or more.
[0160] Antioxidants can be added to these hydrocarbon waxes, as long as the aforementioned effects are not impaired. The amount of hydrocarbon wax relative to 100.0 parts by weight of binder resin is preferably 1.0 to 30.0 parts by weight, and more preferably 5.0 to 15.0 parts by weight. The melting point of the hydrocarbon wax is preferably 30°C to 120°C, and more preferably 60°C to 100°C.
[0161] <Coloring agent>
[0162] Known pigments and dyes can be used as colorants. From the viewpoint of excellent weather resistance, pigments are preferred as colorants. Examples of cyan colorants include copper phthalocyanine compounds and their derivatives, anthraquinone compounds, and basic dye lake compounds. Specifically, the following can be mentioned: CI Pigment Blue 1, 7, 15, 15:1, 15:2, 15:3, 15:4, 60, 62, and 66.
[0163] Examples of magenta colorants include condensed azo compounds, diketopyrrolopyrrole compounds, anthraquinone compounds, quinacridone compounds, basic lake dye compounds, naphthol compounds, benzimidazolone compounds, thioindigo compounds, and perylene compounds. Specifically, the following can be mentioned: CI Pigment Red 2, 3, 5, 6, 7, 23, 48:2, 48:3, 48:4, 57:1, 81:1, 122, 144, 146, 150, 166, 169, 177, 184, 185, 202, 206, 220, 221, and 254, and CI Pigment Violet 19.
[0164] Examples of yellow colorants include condensed azo compounds, isoindolinone compounds, anthraquinone compounds, azo metal complexes, methine compounds, and allylamide compounds. Specifically, the following can be mentioned: CI Pigment Yellow 12, 13, 14, 15, 17, 62, 74, 83, 93, 94, 95, 97, 109, 110, 111, 120, 127, 128, 129, 147, 151, 154, 155, 168, 174, 175, 176, 180, 181, 185, 191, and 194.
[0165] Examples of black colorants include carbon black and those tinted to black using the aforementioned yellow, magenta, and cyan colorants. These colorants can be used alone or as a mixture of two or more. Furthermore, they can be used in a solid solution state. The amount of colorant is preferably from 1.0 to 20.0 parts by weight relative to 100.0 parts by weight of the binder resin.
[0166] <Manufacturing Method of Toner Granules>
[0167] Toner particles can be produced using any known production method, such as dry polymerization, emulsion polymerization, dissolution-suspension polymerization, and suspension polymerization. To control the presence of the compound of formula (C) near the surface of the toner particles within a specific range, the following processing steps are preferred.
[0168] Preferably, the method for manufacturing toner particles includes a treatment step of treating a toner particle dispersion in an aqueous medium with pH (1) at a temperature above 90°C and then with pH (2), wherein the toner particles obtained by any production method are dispersed.
[0169] pH(1) and pH(2) preferably satisfy the following equations (4) and (5). (Hereinafter referred to as the high temperature and high pH treatment step).
[0170] pH(1) <pH(2) (4)
[0171] 5.5≤pH(2)≤11.0 (5)
[0172] It is believed that through a high-temperature, high-pH treatment step, the terminal carboxylic acids contained in the polyester resin can be oriented towards the surface of the toner particles, and the ester bond segments can be unevenly distributed near the surface of the toner particles. Therefore, the orientation state of the compound of formula (C) can be more precisely controlled, and uneven distribution within 100 nm of the toner particle surface can be promoted. In addition, the selectivity of materials such as polyester resins is improved.
[0173] The preferred temperature is 95°C or higher. There is no particular limit to the upper limit, but it is preferably 110°C or lower, 105°C or lower, and 100°C or lower. By treating at a high temperature of 90°C or higher within the above-mentioned pH range, the orientation state of the molecules in the polyester resin can be easily moved. By making the pH (2) in formula (5) higher than pH (1), the orientation state of the polyester resin immobilized in the obtained toner particles can be easily changed.
[0174] Specifically, when pH (2) in formula (5) is above 5.5, the carboxylic acid at the end of the polyester resin may undergo acid dissociation, allowing the carboxylic acid at the end of the polyester resin to selectively face the surface of the toner particles, and the orientation state can be more precisely controlled. In addition, by setting pH (2) below 11.0, the generation of bubbles that easily cause coarse particles is suppressed, and the production can proceed without quality problems, such as fogging caused by poor charging due to the generated coarse particles.
[0175] The pH (2) is more preferably 6.0 to 10.5. Furthermore, the pH (1) is preferably 3.0 or higher and less than 5.5, and more preferably 4.5 or higher and less than 6.0. The treatment time at pH (1) is preferably about 5 minutes to 6 hours, and more preferably about 30 minutes to 3 hours. The treatment time at pH (2) is preferably about 1 minute to 120 minutes, and more preferably about 10 minutes to 60 minutes.
[0176] When toner particles are produced in an aqueous medium, such as by suspension polymerization or emulsion polymerization, a suspension in which the toner particles are dispersed in the aqueous medium can be obtained. Therefore, it is preferable to use this suspension for high-temperature, high-pH treatment. When toner particles are produced by a dry method, such as pulverization, it is preferable to re-slurry the obtained toner particles to obtain a suspension, and then subject it to the above-described high-temperature, high-pH treatment step.
[0177] Preferably, toner particles are produced by suspension polymerization, in which a polymeric monomer composition is granulated in an aqueous medium to form particles of the polymeric monomer composition. The method for producing toner particles includes a granulation step of forming particles from a polymeric monomer composition comprising polymeric monomers, hydrocarbon waxes, and polyester resins in an aqueous medium, and a polymerization step of obtaining toner particles by polymerizing the polymeric monomers contained in the particles of the polymeric monomer composition. Following the polymerization step, a high-temperature, high-pH treatment step is preferably performed on the obtained toner particles. The toner particles can be obtained by filtering, washing, and drying the toner particles obtained as described above using known methods.
[0178] The following describes in detail a method for producing toner particles by pulverization through examples. Examples of producing toner particles by pulverization are given below.
[0179] In the raw material mixing step, binder resin, hydrocarbon wax, and optional other additives are weighed in predetermined amounts and mixed to form the materials constituting the toner particles. Examples of mixing equipment include double cone mixers, V-type mixers, drum mixers, super mixers, FM mixers, Nauta mixers, and MechanoHybrid (manufactured by Nippon Coke Industries, Ltd.).
[0180] Next, the mixed materials are melt-blended to disperse hydrocarbon waxes and the like in the binder resin. In the melt-blending step, batch mixers such as pressure mixers or Banbury mixers, or continuous mixers, can be used. Single-screw or twin-screw extruders have become mainstream due to their advantages in continuous production. Examples include the KTK twin-screw extruder (manufactured by Kobe Steel, Ltd.), the TEM twin-screw extruder (manufactured by Toshiba Machine Co., Ltd.), the PCM mixer (manufactured by Ikegai Corp.), the twin-screw extruder (manufactured by KCK Engineering Co.), and blending mills (manufactured by Buss AG), Kneadex (manufactured by Nippon Coke Industries Co., Ltd.), etc. Furthermore, the resin composition obtained by melt-blending can be rolled using twin rolls or the like, and cooled with water or the like in the cooling step.
[0181] Then, in the pulverizing step, the cooled product of the resin composition is pulverized to the desired particle size. In the pulverizing step, after coarse pulverization with a pulverizer such as a crusher, hammer mill, or milling mill, it is further finely pulverized, for example, with a Cryptron system (manufactured by Kawasaki Heavy Industries, Ltd.), a super rotor (manufactured by Nisshin Engineering Co., Ltd.), a turbomill (manufactured by Freund-Turbo Corporation), or a fine pulverizer based on air jet method.
[0182] Subsequently, as needed, the toner particles are classified using classifiers or screening machines such as the Elbow Jet inertial classification system (manufactured by Nittetsu Mining Co., Ltd.), the Turboplex centrifugal classification system (manufactured by Hosokawa Micron Corporation), the TSP separator (manufactured by Hosokawa Micron Corporation), and the Faculty (manufactured by Hosokawa Micron Corporation).
[0183] Preferably, the obtained toner particles are re-slurryed and subjected to the above-described high-temperature, high-pH treatment. The toner particles can then be obtained by filtration, washing, and drying using known methods.
[0184] The following will describe in detail, through examples, a method for producing toner particles by emulsification and aggregation.
[0185] (Preparation process of binder resin particle dispersion)
[0186] For example, a dispersion of binder resin particles can be prepared in the following manner. When the binder resin is a homopolymer or copolymer of vinyl monomers (vinyl resin), the vinyl monomers are subjected to emulsification polymerization and seed polymerization in an ionic surfactant to prepare a dispersion in which the vinyl resin particles are dispersed in an ionic surfactant.
[0187] When the binder resin is a resin other than a vinyl resin, such as a polyester resin, the resin is mixed with an aqueous medium in which an ionic surfactant or a polyelectrolyte is dissolved. The solution is then heated above the resin's melting or softening point to dissolve the resin, and a dispersion in which the binder resin particles are dispersed in the ionic surfactant is prepared using a disperser with strong shear force, such as a homogenizer.
[0188] There are no particular limitations on the dispersion method, and examples include known dispersers such as ball mills, sand mills, and bead mills with rotary shear homogenizers and media. However, phase inversion emulsification can also be used as a method for preparing dispersions. In phase inversion emulsification, the binder resin is dissolved in an organic solvent, and a neutralizing agent or dispersing stabilizer is added as needed. An aqueous solvent is then added dropwise under stirring to obtain emulsified particles, and the organic solvent is then removed from the resin dispersion to obtain an emulsion. The order in which the neutralizing agent and dispersing stabilizer are added can be varied.
[0189] In emulsion aggregation, colorant particle dispersions may be used as needed. Colorant particle dispersions are formed by dispersing at least colorant particles in a dispersant. In emulsion aggregation, wax particle dispersions are used. Wax particle dispersions are formed by dispersing at least hydrocarbon waxes in a dispersant.
[0190] (Gathering Steps)
[0191] The aggregation step of forming aggregated particles is the step of forming aggregated particles, wherein the aggregated particles include binder resin particles, hydrocarbon wax particles, and colorant particles that are added as needed to an aqueous medium comprising binder resin particles, hydrocarbon wax particles, and colorant particles as needed.
[0192] (Fusion step)
[0193] In the fusion step, the obtained aggregated particles are heated and fused together. Before transitioning to the fusion step, pH adjusters, polar surfactants, and non-polar surfactants may be added appropriately to prevent the fusion of toner particles.
[0194] The heating temperature can be equal to or higher than the glass transition temperature of the resin contained in the aggregated particles (or, when more than two resins are present, the glass transition temperature of the resin with the highest glass transition temperature) and lower than the decomposition temperature of the resin. Therefore, the heating temperature varies depending on the type of resin in the binder resin particles and cannot be defined unconditionally, but is generally from the glass transition temperature of the resin contained in the aggregated particles to 140°C. Heating can be performed using heating devices / appliances known per se.
[0195] If the heating temperature is high, a short fusion time is sufficient, while if the heating temperature is low, a long fusion time is required. That is, the fusion time depends on the heating temperature and cannot be defined unconditionally, but it is typically between 30 minutes and 10 hours.
[0196] Toner particles can be obtained by performing the dispersion preparation, aggregation, and fusion steps described above. The obtained toner particles can be used as is for further steps, such as filtration, washing, and drying, by known methods. Preferably, the obtained toner particles are subjected to high-temperature, high-pH treatment. Then, the toner particles can be obtained by filtration, washing, and drying by known methods.
[0197] Toners can be obtained by externally adding inorganic fine particles, including fine silica particles, and mixing them with the obtained toner particles using known methods. Known mixers, such as the FM mixer (manufactured by Nippon Coke Co., Ltd.), can be used for both external addition and mixing.
[0198] <Various Measurement Methods>
[0199] The following describes various measurement methods.
[0200] <Method for measuring trimethylsilanol content in fine silica particles by headspace analysis>
[0201] The amount of trimethylsilanol in the fine silica particles was measured using the fine silica particles separated from the toner.
[0202] (Method for separating fine silica particles from the surface of toner)
[0203] When fine silica particles separated from the surface of toner particles are used as a measurement sample, the fine silica particles are separated from the toner through the following steps. Furthermore, toner particles excluding external additives can also be obtained by the following separation method, and the obtained toner particles can be used in various measurement methods.
[0204] (In the case of non-magnetic toners)
[0205] A total of 160 g of sucrose (manufactured by Kishida Chemical Co., Ltd.) was added to 100 mL of ion-exchanged water and dissolved in a water bath to prepare a sucrose concentrate. A dispersion was prepared by placing a total of 31 g of the sucrose concentrate and 6 mL of Contaminone N (a 10% by mass aqueous solution of a neutral detergent for precision instrument cleaning with a pH of 7, consisting of nonionic surfactants, anionic surfactants, and organic auxiliaries, manufactured by Wako Pure Chemical Industries, Ltd.) in a centrifuge tube. 1 g of toner was added to the dispersion, and the toner clumps were loosened using a spatula or similar tool.
[0206] The centrifuge tubes were placed on a "KM Shaker" (model: V.SX) manufactured by Iwaki Sangyo Co., Ltd., and the tubes were shaken for 20 minutes at 350 reciprocations per minute. After shaking, the solution was transferred to a glass tube (50 mL) for oscillating the rotor and centrifuged at 3500 rpm for 30 minutes.
[0207] In the glass tube after centrifugation, the toner particles are present in the uppermost layer, and the fine silica particles are present in the lower aqueous solution layer. The lower aqueous solution is collected, and centrifugation is repeated as needed. After thorough separation, the dispersion is dried, and the fine silica particles are collected. Furthermore, the toner particles in the upper layer are collected, filtered, and washed with 2 L of deionized water heated to 40°C. The washed toner particles are then removed.
[0208] (Regarding magnetic toners)
[0209] A total of 6 mL of Contaminone N (a 10% by mass aqueous solution of a neutral detergent for precision instrument cleaning, consisting of nonionic surfactants, anionic surfactants, and organic additives, with a pH of 7, manufactured by Wako PureChemical Industries, Ltd.) was added to 100 mL of deionized water to prepare a dispersion medium. 5 g of toner was added to this dispersion medium, and the mixture was dispersed for 5 minutes using an ultrasonic disperser (VS-150, manufactured by AS ONE Corporation). Subsequently, the dispersion was placed on a "KM Shaker" (model: V.SX) manufactured by Iwaki Sangyo Co., Ltd., and the dispersion was agitated at 350 reciprocations per minute for 20 minutes.
[0210] Subsequently, neodymium magnets were used to confine the toner particles. Since the fine silica particles were present in the upper aqueous solution, the upper aqueous solution was collected, and magnetic separation was repeated as needed. After thorough separation, the dispersion was dried to collect the fine silica particles. The toner particles confined using neodymium magnets were also collected. The toner particles were washed with 2 L of flowing ion-exchanged water heated to 40°C, and the washed toner particles were removed.
[0211] (Measurement of the amount of trimethylsilanol in fine silica particles)
[0212] The amount of trimethylsilanol in the fine silica particles was determined by headspace analysis of the volatile organic components of the fine silica particles at a heating temperature of 150°C, and the concentration was calculated based on the mass of the fine silica particles, converted to octamethyltrisiloxane. The measurement conditions are shown below.
[0213] Measurements were performed using multiple headspace extraction (MHE). In MHE, the sample is contained in a sealed container with a predetermined volume, the container is heated as needed, and the gas phase within the sealed container is extracted. Measurements were performed using a headspace sampler HS40XL manufactured by PerkinElmer Japan Co., Ltd., and TRACE GC and TRACEMS (manufactured by Thermoquest Co., Ltd.) for GC / MS. Sample vials were connected to the gas chromatograph.
[0214] (i) Headspace sampler conditions
[0215] - Sample volume: 500 mg
[0216] Sample temperature: 150℃
[0217] Needle temperature: 150℃
[0218] - Transmission line temperature: 180℃
[0219] - Duration: 60 minutes
[0220] -Pressurization time: 0.25 minutes
[0221] Injection time: 0.08 minutes
[0222] (ii) GC conditions
[0223] - Column: HP5-MS (0.25mm, 60m)
[0224] - Column temperature: Hold at 40°C for 3 minutes, then increase from 40°C to 70°C at 2.0°C / min, from 70°C to 150°C at 5.0°C / min, and from 150°C to 300°C at 10.0°C / min.
[0225] -Split ratio 50:1
[0226] (iii) Appliances
[0227] A headspace analysis glass vial manufactured by PerkinElmer Japan Co., Ltd. will be used as a sealed container.
[0228] (iv) Method
[0229] (1) Preparation of standard samples
[0230] First, an acetone solution with a concentration of 1000 ppm of octamethyltrisiloxane was prepared as a standard sample of trimethylsilanol. 5 μL of the solution was placed in a glass bottle using a 10 μL microsyringe, and the bottle was quickly sealed with a high-temperature analytical septum.
[0231] (2) Preparation of fine silica particle samples
[0232] A total of 50 mg of fine silica particles was placed in a glass bottle and sealed with a high-temperature analytical septum to prepare the sample.
[0233] (v) Analysis
[0234] Standard samples of octamethyltrisiloxane solution were measured using quantitative multiple headspace extraction (QHEED) to determine the total peak area per 0.005 μL of octamethyltrisiloxane (because GC sensitivity varies daily, the peak area per 0.005 μL of octamethyltrisiloxane needs to be studied for each measurement). Vaporized components were introduced into a mass spectrometer (mass analyzer), and the obtained peaks were confirmed to originate from octamethyltrisiloxane.
[0235] Next, the silica fine particles were measured in the same manner as with octamethyltrisiloxane, and introduced into a mass spectrometer to identify the peak of trimethylsilanol, and the total peak area was calculated. The amount of trimethylsilanol in the measured sample was calculated from the peak area of the octamethyltrisiloxane standard sample calculated proportionally, and the amount of trimethylsilanol in the silica fine particles was obtained.
[0236] <Method for measuring ion quantity (secondary ion mass / secondary ion charge number (m / z)) by time-of-flight secondary ion mass spectrometry (TOF-SIMS)>
[0237] To determine the concentration distribution of functional groups represented by formula (C) on the surface of toner particles, firstly, the structure represented by formula (C) contained in the polar resin, such as polyester resin, of the toner particles is identified. Next, using TOF-SIMS, the amount of ions of the monomer units based on the acid component is measured among the alcohol-based monomer units and the acid-based monomer units constituting the structure (ester bond) represented by formula (C) contained in the polar resin.
[0238] (1) Identification of the structure represented by formula (C) contained in the polar resin of the toner particles
[0239] Accurately weigh approximately 1.5g of toner granules (X1[g]), place them in a pre-weighed cylindrical filter paper (trade name: No.86R, size 28×100mm, manufactured by Advantech Toyo Co., Ltd.), and place it in a Soxhlet extractor.
[0240] Extraction was performed using 200 mL of vinyl acetate as the solvent for 18 hours. During this time, extraction was carried out at reflux, with the solvent circulating every 5 minutes. After extraction, the extract was collected, air-dried, and then vacuum-dried at 50°C for 24 hours. Because vinyl acetate has ester groups and is highly polar, polar resins with ester groups, such as polyester resins, can be extracted in the same manner.
[0241] The composition of polar resins in toner particles was analyzed by NMR spectroscopy.
[0242] Nuclear magnetic resonance spectroscopy analysis was performed using samples obtained by drying the vinyl acetate extract. 1 ¹H-NMR [400MHz, CDCl₃, room temperature (25℃)]. Analytical conditions are as follows.
[0243] Measuring apparatus: JNM-EX400 FT NMR instrument (manufactured by JEOL Ltd.)
[0244] Measurement frequency: 400MHz
[0245] Pulse condition: 5.0 μs
[0246] Frequency range: 10500Hz
[0247] Total number of times: 64
[0248] The composition of the polar resin is analyzed by the NMR spectrum measured by the above method, and the structure represented by formula (C) contained in the polar resin is identified.
[0249] (2) Measurement of ion quantity using TOF-SIMS
[0250] For the measurement of ion quantity (peak intensity) using TOF-SIMS, TRIFT-IV manufactured by ULVAC-PHI, Inc. was used.
[0251] The analysis conditions are as follows.
[0252] Sample preparation: Adhere the toner to the indium sheet.
[0253] Sample pretreatment: None
[0254] Primary ion: Au ion
[0255] Accelerating voltage: 30kV
[0256] Charge neutralization mode: On
[0257] Measurement mode: Positive
[0258] Grating: 200μm
[0259] Measurement time: 60s
[0260] Typically, TOF-SIMS is a surface analysis method, and the data in the depth direction involves approximately 1 nm. Therefore, the intensity within the toner particles was measured by sputtering the toner particles with argon cluster ions and then scratching the surface. The sputtering conditions are as follows.
[0261] Accelerating voltage: 10kV
[0262] Current: 3.4nA
[0263] Grating: 600μm
[0264] Irradiation time: 5s
[0265] In the depth measurement, a polymethyl methacrylate (PMMA) film was sputtered under the same conditions beforehand to confirm the relationship with irradiation time, and it was confirmed that 100 nm could be removed within an irradiation time of 300 s. The ion quantity at a depth of 100 nm from the surface of the toner particles was the value measured after 60 sputtering cycles under the above conditions. Furthermore, the ion quantity on the surface of the toner particles (depth 0 nm) was the value measured using toner particles from which external additives had been removed by the above method, without sputtering the toner particles.
[0266] Standard value, A(dmax) calculation / definition: The total mass count of the acid-based monomer units constituting the structure (ester bond) represented by formula (C) in the polar resin, as defined by component analysis according to ULVAC-PHI standard software (Win Cadence), is taken as the ionic quantity (secondary ion mass / secondary ion charge (m / Z)) of the structure represented by formula (C). The value obtained by dividing this ionic quantity by the total number of counted ions is defined as the standard value.
[0267] As described above, the standard value on the outermost surface of the toner particles, from which external additives have been removed, is defined as A(0). Furthermore, under the aforementioned sputtering conditions, the surface of the toner particles was scratched with an irradiation time of 5 seconds, and the operation of obtaining standard values was repeated for a total of 300 seconds (i.e., to a depth of 100 nm), and standard values were obtained from the surface of the toner particles to a depth of 100 nm. The standard value at a position 100 nm from the surface of the toner particles is defined as A(100).
[0268] Furthermore, among the standard values measured from the surface of the toner particles to 100 nm, the standard value that is larger than A(0) and A(100) and has a factor at least 1.05 greater than A(0) and A(100) is defined as a peak. The largest peak among the obtained peaks is defined as A(dmax). Therefore, when the standard values have peaks, the number of peaks can range from 1 to 58. A schematic diagram of the analytical results is shown in... Figure 2 middle.
[0269] <Methods for measuring molecular weight>
[0270] For example, the molecular weight of resins such as polyester resins is measured by gel permeation chromatography (GPC) as follows: First, the polyester resin is dissolved in tetrahydrofuran (THF) at room temperature. Then, the obtained solution is filtered through a solvent-resistant membrane filter "Maeshori Disc" (manufactured by Tosoh Corporation) with a pore size of 0.2 μm to obtain a sample solution. The sample solution is adjusted so that the concentration of the component soluble in THF is 0.8% by mass. This sample solution is then used for measurement under the following conditions.
[0271] Device: High-speed GPC device "HLC-8220GPC" (manufactured by Tosoh Corporation)
[0272] Column: Two sets of LF-604
[0273] Elution buffer: THF
[0274] Flow rate: 0.6 ml / min
[0275] Oven temperature: 40℃
[0276] Sample injection volume: 0.020 ml
[0277] In calculating the molecular weight of the samples, molecular weight calibration curves were plotted using standard polystyrene resins (e.g., trade names "TSK Standard Polystyrene F-850, F-450, F-288, F-128, F-80, F-40, F-20, F-10, F-4, F-2, F-1, A-5000, A-2500, A-1000, A-500", manufactured by Tosoh Corporation).
[0278] <Acid value of polyester resin>
[0279] Acid value is the number of milligrams of potassium hydroxide required to neutralize the acid contained in 1g of sample. Acid value is measured according to JIS K0070-1992, but specifically, it is measured according to the following steps.
[0280] Titration was performed using a 0.1 mol / L potassium hydroxide ethanol solution (manufactured by Kishida Chemical Co., Ltd.). The coefficient of the potassium hydroxide ethanol solution was determined using a potentiometric titration apparatus (AT-510 potentiometric titration measuring apparatus manufactured by Kyoto Electronics Manufacturing Co., Ltd.). A total of 100 mL of 0.100 mol / L hydrochloric acid was taken into a 250 mL high-pressure beaker, titrated with the potassium hydroxide ethanol solution, and the coefficient was determined by the amount of potassium hydroxide ethanol solution required for neutralization. 0.100 mol / L hydrochloric acid prepared according to JIS K8001-1998 was used.
[0281] The following shows the measurement conditions for acid value measurement.
[0282] Titration apparatus: Potentiometric titration apparatus AT-510 (manufactured by Kyoto Electronics Manufacturing Co., Ltd.)
[0283] Electrode: Composite glass electrode, double junction type (manufactured by Kyoto Electronics Manufacturing Co., Ltd.)
[0284] Titrator control software: AT-WIN
[0285] Titration analysis software: Tview
[0286] The titration parameters and control parameters during titration are as follows.
[0287] (Titration parameters)
[0288] Titration mode: Blank titration
[0289] Titration method: Total titration
[0290] Maximum titration: 20 ml
[0291] Waiting time before titration: 30 seconds
[0292] Titration direction: Automatic
[0293] (Control parameters)
[0294] Endpoint determination potential: 30dE
[0295] endpoint determination potential value: 50 dE / dmL
[0296] Endpoint detection and determination: Not set
[0297] Speed control mode: Standard
[0298] Gain: 1
[0299] Data acquisition potential: 4mV
[0300] Data acquisition titration amount: 0.1 ml
[0301] Main experiment: Accurately weigh 0.100g of the sample into a 250ml high-pressure beaker, add 150ml of a toluene / ethanol (3:1) mixture, and dissolve within 1 hour. Titrate using a potentiometric titrator with potassium hydroxide ethanol solution.
[0302] Blank test: Perform a titration similar to the steps described above, except that no sample was used (i.e., only a toluene / ethanol (3:1) mixture was used). The acid value was calculated by substituting the obtained results into the following formula.
[0303] A = [(CB) × f × 5.611] / S
[0304] (In the formula, A: acid value (mgKOH / g), B: amount of potassium hydroxide ethanol solution added in the blank experiment (ml), C: amount of potassium hydroxide ethanol solution added in the main experiment (ml), f: potassium hydroxide solution factor, S: sample mass (g)).
[0305] <Identification and Quantification Methods of Polyester Resin Monomer Units in Toner Particles>
[0306] For analysis, pyrolysis gas chromatography-mass spectrometry (hereinafter referred to as pyrolysis GC / MS) and NMR were used. Components with a molecular weight of 1500 or higher were selected for measurement. This is because regions with molecular weights less than 1500 are considered to contain a high proportion of wax and almost no resin components.
[0307] In pyrolysis GC / MS, the constituent monomer units of the total resin in the toner can be determined, and the peak area of each monomer unit can be measured. However, for quantification, a sample with known concentration is required as a reference to normalize the peak intensity. Meanwhile, in NMR, the constituent monomer units can be identified and quantified without using a sample with known concentration. Therefore, depending on the situation, the constituent monomer units can be determined by comparing the spectra of NMR and pyrolysis GC / MS. Specifically, when the amount of resin component in the deuterated chloroform used as the extraction solvent in NMR measurement is less than 5.0% by mass, quantification is performed by NMR measurement.
[0308] Simultaneously, when the resin component, which is insoluble in deuterated chloroform used as the extraction solvent during NMR measurement, is present in an amount of 5.0% by mass or more, NMR and pyrolysis GC / MS measurements are performed on the soluble components of deuterated chloroform, and pyrolysis GC / MS measurements are performed on the insoluble components of deuterated chloroform. In this case, firstly, NMR measurements of the soluble components of deuterated chloroform are performed, and the constituent monomer units are identified and quantified (quantification result 1).
[0309] Next, pyrolysis GC / MS measurements were performed on the deuterated chloroform soluble components, and the peak areas attributable to each constituent unit were determined. Using the quantitative result 1 obtained by NMR measurements, the relationship between the amount of each constituent unit and the peak areas of the pyrolysis GC / MS was determined. Next, pyrolysis GC / MS measurements were performed on the deuterated chloroform insoluble components, and the peak areas attributable to each constituent unit were determined. Based on the relationship between the amount of each constituent unit obtained by measuring the deuterated chloroform soluble components and the peak areas of the pyrolysis GC / MS, the constituent units in the deuterated chloroform insoluble components were quantified (quantification result 2). Then, quantification result 1 and quantification result 2 were combined to obtain the final quantitative result for each constituent unit. Specifically, the following operations were performed.
[0310] (1) Weigh a total of 500 mg of toner into a 30 mL glass sample bottle, add 10 mL of deuterated chloroform, cap the bottle, and disperse and dissolve the toner using an ultrasonic disperser for 1 hour. Then, filter the solution through a 0.4 μm diameter membrane filter and collect the filtrate. At this point, the insoluble components of deuterated chloroform remain on the membrane filter.
[0311] (2) Using high-performance liquid chromatography (HPLC), components with a molecular weight less than 1500 were removed from the 3 mL filtrate using a fraction collector, and the resin solution from which the components with a molecular weight less than 1500 were removed was collected. Chloroform was removed from the collected solution using a rotary evaporator to obtain the resin. Components with a molecular weight less than 1500 were determined by pre-measuring polystyrene resin with a known molecular weight and obtaining the elution time.
[0312] (3) Dissolve the total 20 mg of resin obtained in 1 mL of deuterated chloroform and proceed with the reaction. 1 H-NMR measurements are performed, and the spectra are attributed to the constituent monomers of adhesive resins such as polyester resins and vinyl resins, and quantitative values are obtained.
[0313] (4) If it is necessary to analyze the insoluble components of deuterated chloroform, the analysis shall be performed by pyrolysis GC / MS. Derivatization treatments such as methylation may be performed as needed.
[0314] (NMR measurement conditions)
[0315] Measuring device: Bruker AVANCE 500, manufactured by Bruker Biospin Co., Ltd.
[0316] Measurement nucleus: 1 H
[0317] Measurement frequency: 500.1MHz
[0318] Total number of times: 16
[0319] Temperature measured: room temperature
[0320] (Measurement conditions for pyrolysis GC / MS)
[0321] Pyrolysis unit: TPS-700, manufactured by Nippon Analytical Industry Co., Ltd.
[0322] Pyrolysis temperature: an appropriate value between 400℃ and 600℃, in this case 590℃
[0323] GC / MS instrument: ISQ, manufactured by Thermo Fisher Scientific Co., Ltd.
[0324] Column: "HP5-MS" (Agilent / 19091S-433), length 30m, inner diameter 0.25mm, film thickness 0.25μm
[0325] GC / MS conditions
[0326] Injection port conditions:
[0327] Inlet temperature: 250℃
[0328] Flow rate: 50ml / minute
[0329] GC heating conditions: 40℃ (5 minutes) → 10℃ / minute (300℃) → 300℃ (20 minutes)
[0330] Mass range: m / z = 10 to 550
[0331] <Methods for Calculating Shell Thickness in Core-Shell Structures>
[0332] Cross-sectional observation of the toner using a transmission electron microscope (TEM) can be performed in the following ways.
[0333] First, the toner was sprayed onto a coverslip (Matsunami Glass Co., Ltd., corner coverslip, square No. 1) to form a single layer, and an Os film (5nm) and a naphthalene film (20nm) were applied as protective films using an osmium plasma coating machine (filgen Co., Ltd., OPC80T). Next, a PTFE tube (inner diameter Φ1.5mm × outer diameter Φ3mm × 3mm) was filled with photocurable resin D800 (JEOL Ltd.), and the coverslip was gently placed on the tube, oriented so that the toner was in contact with the photocurable resin D800. After the resin was cured by light irradiation in this state, the coverslip and the tube were removed to form a cylindrical resin with the toner embedded in the outermost surface.
[0334] Using an ultrasonic microtome (Leica Biosystems Nussloch GmbH, UC7), a layer equal to half the diameter of the toner particles (4.0 μm when the weight-average particle size (D4) is 8.0 μm) was cut from the outermost surface of the cylindrical resin at a cutting speed of 0.6 mm / s to expose the cross-section of the toner particles. Next, magnetic toner was cut to a film thickness of 250 nm, and non-magnetic toner was cut to a film thickness of 70 nm to prepare thin-film samples of the toner particle cross-section. By cutting in this manner, the cross-section of the central portion of the toner particles can be obtained.
[0335] Subsequently, the elemental composition of the cross-sections of the obtained toner particles was analyzed using energy-dispersive X-ray spectroscopy (EDX) to prepare EDX mapping images. The shell layers were observed from the cross-section of the toner using a transmission electron microscope (JEM-2800, manufactured by JEOL Ltd.) (TEM-EDX) with a magnification set to 40,000 to 50,000, and elemental mapping was performed using EDX. In the EDX mapping images, signals originating from the elemental composition of the shell material were confirmed in the profile of the toner particle cross-section, and the presence or absence of the shell was confirmed. The mapping conditions were a retention rate of 9,000 to 13,000 and a cumulative number of 120.
[0336] In the EDX-mapped image, the profile and center point of the toner particle cross-section are obtained. It is assumed that the cross-section of the observed toner particle shows a major axis R (μm) satisfying the relationship 0.9 ≤ R / D4 ≤ 1.1 with respect to the weight-average particle size (D4) of the toner. It is assumed that the profile of the toner particle cross-section follows the surface of the toner particle observed in the EDX-mapped image. It is assumed that the center point of the toner particle cross-section is the geometric center of the toner particle cross-section. A line is drawn from the obtained center point to the profile of the toner particle cross-section. The line is drawn to form an orthogonal cross at the center point of the cross-section. The shell thickness is measured at four points at the ends of the intersecting lines in a toner particle cross-section. In the toner particle cross-section, the signal portion originating from the constituent elements of the shell material is taken as the shell. A total of 100 toner cross-sections are observed, and the average shell thickness is calculated.
[0337] <Method for measuring the number-average particle size of primary particles of fine silica>
[0338] The number-average particle size (D1) of the primary particles of silica fines was calculated from images of silica fines on the toner surface taken by a Hitachi S-4800 ultra-high resolution field emission scanning electron microscope (Hitachi High-Technologies Corporation). The image acquisition conditions for the S-4800 were as follows.
[0339] (1) Sample preparation
[0340] A thin layer of conductive paste is applied to the sample stage (15mm x 6mm aluminum sample stage), and then toner is sprayed onto it. Further blowing is performed to remove excess toner from the sample stage and toner is allowed to dry completely. The sample stage is then positioned in the sample holder, and its height is adjusted to 36mm using a sample height gauge.
[0341] (2) Observation conditions settings in S-4800
[0342] The number-average particle size of the primary particles of silica fines was calculated using images obtained through backscattered electron imaging in an S-4800. Since backscattered electron imaging contains fewer charged silica fines than secondary electron imaging, the particle size of silica fines can be measured with high precision.
[0343] Inject liquid nitrogen into the contamination trap inside the S-4800 housing until nitrogen overflows, and leave the microscope in place for 30 minutes. Start the S-4800's "PC-SEM" and perform a rinse (cleaning of the FE chip used as the electron source). Click the acceleration voltage display on the control panel and press the [Rinse] button to open the rinse execution dialog box. Confirm the rinse intensity is 2 and perform the rinse. Confirm the emission current generated by the rinse is between 20 μA and 40 μA. Insert the sample holder into the sample chamber of the S-4800 housing. Press [Origin] on the control panel to move the sample holder to the observation position.
[0344] Click the accelerating voltage display section to open the HV settings dialog box, set the accelerating voltage to [0.8kV] and the emission current to [20μA]. In the [Basic] option of the operation panel, set the signal selection to [SE], select [U+] and [+BSE] for the SE detector, and select [LA100] in the selection box to the right of [+BSE] to set the backscattered electron image observation mode. Similarly, in the [Basic] option of the operation panel, set the probe current of the photoelectric system condition block to [Normal], set the focus mode to [UHR], and set WD to [3.0mm]. Press the [On] button on the accelerating voltage display section of the control panel to apply the accelerating voltage.
[0345] (3) Calculation of the number-average particle size (D1) of fine silica particles
[0346] Drag the zoom section of the control panel inwards to set the magnification to 100,000 (100k) times. Rotate the focus knob [Coarse] on the operation panel and adjust the aperture to a certain degree of focus. Click [Align] on the control panel to display the alignment dialog box and select [Beam]. Rotate the STIGMA / ALIGNMENT knob (X, Y) on the operation panel to move the displayed beam to the center of the concentric circles. Next, select [Aperture] and gradually rotate the STIGMA / ALIGNMENT knob (X, Y) to stop the image movement or adjust it to the minimum movement. Close the aperture dialog box and focus with autofocus. Repeat this operation twice more to focus.
[0347] Subsequently, the particle size of at least 300 silica fine particles on the surface of the toner was measured to obtain the average particle size. Here, since some silica fine particles also exist as aggregates, the maximum diameter of the particles that can be identified as primary particles was obtained, and the arithmetic mean of the obtained maximum diameters was used to obtain the number-average particle size of the primary particles of silica fine particles.
[0348] <Method for measuring the weight-average particle size (D4) of toners>
[0349] The weight-average particle size (D4) and number-average particle size (D1) of the toner were measured using a precision particle size distribution measuring device based on pore resistance and equipped with a 100 μm orifice, the "Coulter Counter Multisizer 3" (registered trademark, manufactured by Beckman-Coulter Inc.), and dedicated software, "Beckman Coulter Multisizer 3 Version 3.51" (manufactured by Beckman-Coulter Inc.), with 25,000 effective measurement channels. The measurement data were analyzed and calculations were performed. The electrolyte aqueous solution used for measurement could be prepared by dissolving super-grade sodium chloride in ion-exchanged water to a concentration of approximately 1% by mass. For example, "ISOTON II" (manufactured by Beckman-Coulter Inc.) could be used. The dedicated software was set up as follows before measurement and analysis.
[0350] On the "Change Standard Measurement Method (SOM) Screen" of the dedicated software, set the total count in the control mode to 50,000 particles, the number of measurement cycles to 1, and the Kd value to the value obtained using "Standard Particle 10.0 μm" (manufactured by Beckman-Coulter Inc.). The threshold and noise level are automatically set by pressing the threshold / noise level measurement button. Additionally, set the current t to 1600 μA, the gain to 2, and the electrolyte to ISOTONII, and check the post-measurement tube rinsing option. On the "Pulse to Particle Size Conversion Setting Screen" of the dedicated software, set the element spacing to logarithmic particle size, the particle size element to 256 particle size elements, and the particle size range to 2 μm to 60 μm. The specific measurement method is as follows.
[0351] 1. Place approximately 200 mL of the above electrolyte solution into a 250 mL glass round-bottom beaker provided with the Multisizer 3, place the beaker on the sample stage, and stir counterclockwise at 24 rpm using a stir bar. Then, remove contaminants and air bubbles from the nozzle using the "Venere Rinse" function in the dedicated software.
[0352] 2. Place approximately 30 ml of electrolyte aqueous solution into a 100 ml flat-bottomed glass beaker and add approximately 0.3 mL of a diluent prepared by diluting "Contaminone N" (a 10% by mass aqueous solution of a precision instrument cleaning neutral detergent consisting of nonionic surfactants, anionic surfactants, and organic additives, with a pH of 7, manufactured by Wako Pure Chemical Industries, Ltd.) three times by mass with ion-exchanged water as a dispersant.
[0353] 3. Place the predetermined amount of ion-exchanged water into a water tank equipped with an "Ultrasonic Dispersion System Tetora 150" (manufactured by Nikkaki Bios Co., Ltd.) containing two oscillators with a 50kHz oscillation frequency, a 180-degree phase offset, and a power output of 120W, and add approximately 2 mL of Contaminone N to the water tank.
[0354] 4. Place the beaker from step 2 into the beaker fixing hole of the ultrasonic disperser and start the ultrasonic disperser. Adjust the height of the beaker to maximize the resonance state of the electrolyte solution surface in the beaker.
[0355] 5. While irradiating the electrolyte solution in the beaker from step 4 with ultrasound, add approximately 10 mg of colorant little by little to the electrolyte solution and disperse. Then, continue the ultrasonic dispersion treatment for another 60 seconds. During ultrasonic dispersion, adjust the water temperature in the bath appropriately to 10°C to 40°C.
[0356] 6. Using a pipette, add dropwise the electrolyte aqueous solution containing the toner from step 5 to the round-bottom beaker from step 1 mounted on the sample stage, and adjust the concentration to approximately 5%. Then, perform measurements until the number of particles measured reaches 50,000.
[0357] 7. Analyze the measurement data using the dedicated software provided by the device, and calculate the weight-average particle size (D4) and number-average particle size (D1). When setting the chart / number% and chart / volume% using the dedicated software, the "arithmetic mean diameter" on the analysis / number statistics (arithmetic mean) screen and the analysis / volume statistics (arithmetic mean) screen are the number-average particle size (D1) and the weight-average particle size (D4), respectively.
[0358] Example
[0359] The present invention will now be described in more detail with reference to embodiments and comparative examples, but the invention is not limited thereto. Unless otherwise stated, the portions used in the embodiments are based on mass.
[0360] <Production Example of Fine Silica Particles 1>
[0361] A total of 100 parts of fumed silica (silica-based material; spherical, BET specific surface area: 300 m²) were used. 2 / g) was placed in a reaction vessel, and under nitrogen purging and stirring, 20 parts of polydimethylsiloxane (represented by formula (A) with a kinematic viscosity of 50 mm at 25°C) were added. 2A solution obtained by dissolving (with an average number of repeating units n = 60) in 100 parts hexane was first treated at the reaction temperature and reaction time shown in treatment condition 1 of Table 1 while stirring. Then, a solution obtained by diluting 10 parts of polydimethylsiloxane represented by formula (B) as shown in treatment condition 2 of Table 1 with 100 parts hexane was added, and the treatment was carried out at the reaction temperature and reaction time shown in treatment condition 2 of Table 1. The obtained silica fine particles were then pulverized using a pin-type pulverizer to obtain silica fine particles 1. The number average particle size of the primary particles of the obtained silica fine particles 1 was 8 nm. Table 1 shows the physical properties of silica fine particles 1.
[0362] <Production examples of silica fine particles 2 to 12>
[0363] Except for changing the processing conditions 1 (amount of polydimethylsiloxane added, reaction temperature, and reaction time) and processing conditions 2 (type and amount of polydimethylsiloxane added, reaction temperature, and reaction time) in the production example of silica fine particles 1 as described in Table 1, silica fine particles 2 to 12 are produced in the same manner as in the production example of silica fine particles 1. Table 1 shows the physical properties.
[0364] [Table 1]
[0365]
[0366] In the table, BET represents "the BET specific surface area of the raw material, [m²]". 2 Rtemp represents the reaction temperature [°C], and RT represents the reaction time [minutes].
[0367] Furthermore, in the table, "(A) parts" refers to the number of parts of polydimethylsiloxane represented by formula (A) used to treat 100 parts of silica-based material (i.e., fine silica particles before surface treatment). "(B) parts" refers to the number of parts of polydimethylsiloxane represented by formula (B) used to treat 100 parts of silica-based material. "PD" indicates the number average particle size of the primary particles, and "A" indicates the amount of trimethylsilanol (ppm).
[0368] <Production Example of Polyester Resin 1>
[0369] A mixture of 100 parts of raw material monomers (excluding trimellitic anhydride) and 0.52 parts of di(2-ethylhexanoate)tin as a catalyst, prepared in the amounts shown in Table 2, was placed in a polymerization tank equipped with a nitrogen inlet line, a dehydration line, and a stirrer. Next, the atmosphere inside the polymerization tank was converted to a nitrogen atmosphere, and a polycondensation reaction was carried out at 200°C for 6 hours. Furthermore, after raising the temperature to 210°C, trimellitic anhydride was added, the pressure inside the polymerization tank was reduced to 40 kPa, and then the polycondensation reaction was further carried out. Table 2 shows the acid value and molecular weight of the obtained resin.
[0370] <Production Examples of Polyester Resins 2 to 9>
[0371] Polyester resins 2 to 9 were produced using the raw material monomer feed amounts shown in Table 2 in the production example of polyester resin 1, and by performing the same operations as in the production of polyester resin 1. During this process, samples were taken and measured sequentially, and when the desired molecular weight was reached, the polymerization reaction was stopped and the resin was removed from the polymerization tank. Table 2 shows the physical properties of the obtained resins.
[0372] In polyester resins 4, 7, and 9, 2 mol bisphenol A propylene oxide adduct and 3 mol bisphenol A ethylene oxide adduct are used as BPA in a molar ratio of 80.0 to 20.0. Unless otherwise specified, 2 mol bisphenol A propylene oxide adduct is used as BPA.
[0373] [Table 2]
[0374]
[0375] *The symbols for monomer composition indicate the percentage by mass (%) when the mass of the polyester composition is 100. The unit for acid value is mgKOH / g.
[0376] The abbreviations in the table above are as follows:
[0377] TPA: Terephthalic acid
[0378] TMA: Trimericic Acid
[0379] BPA: Bisphenol A propylene oxide or ethylene oxide adduct (details as described above)
[0380] EG: Ethylene glycol
[0381] <Production Example of Styrene-Acrylic Resin 1>
[0382] The following materials are mixed in a reaction vessel equipped with a cooling pipe, a stirrer, and a nitrogen inlet pipe, and heated and maintained at 180°C while being stirred.
[0383]
[0384]
[0385] Subsequently, 50.0 parts by weight of a 2.0% by weight xylene solution of tert-butyl hydroperoxide were continuously added dropwise to the system over 4.5 hours. After cooling, the solvent was separated and removed, and styrene-acrylic resin 1 was synthesized. The weight-average molecular weight (Mw) was 14,500 and the temperature gradient (Tg) was 65°C.
[0386] <Production Example of Polyester Resin Particle Dispersion 1>
[0387] Polyester resin 7 was dispersed using a disperser obtained by modifying a Cavitron CD1010 (manufactured by Eurotec Ltd.) into a high-temperature, high-pressure type. The pH was adjusted to 8.5 with ammonia at a composition ratio of 80% by mass of deionized water and 20% by mass of polyester resin, and the rotor speed was 60 Hz and the pressure was 5 kg / cm². 2 The Cavitron was operated under specific conditions and heated at 140°C using a heat exchanger to obtain a polyester resin particle dispersion. Ion-exchanged water was added to this dispersion to adjust the solid content to 20% by mass, and this was used as polyester resin particle dispersion 1.
[0388] <Production Example of Polyester Resin Particle Dispersion 2 without Organic Solvents>
[0389] A total of 200 parts of a 50% by mass aqueous solution of polyester resin 7 and 0.2 parts of sodium hydroxide were placed into the feed inlet of a twin-screw extruder (TEM-26SS, manufactured by Toshiba Machinery Co., Ltd.). 4.1 parts of a 48.5% by mass aqueous solution of sodium dodecyl diphenyl ether disulfonate (Eleminol MON-7, manufactured by Sanyo Chemical Industries, Ltd.) as a surfactant were added from the fourth barrel of the twin-screw extruder. The mixture was then kneaded at a barrel temperature of 90°C and a screw speed of 400 rpm to combine the polyester resin, sodium hydroxide, and surfactant.
[0390] A total of 150 parts of ion-exchanged water (ion-exchanged water 1) adjusted to 90°C was added from the fifth barrel of the twin-screw extruder, 150 parts of ion-exchanged water (ion-exchanged water 2) adjusted to 90°C was added from the seventh barrel, and 150 parts of ion-exchanged water (ion-exchanged water 3) adjusted to 90°C was added from the ninth barrel. The mixture was then kneaded to obtain an aqueous dispersion of polyester resin particles. Ion-exchanged water was added to this dispersion to adjust the solid content to 20% by mass, and the resulting dispersion was used as polyester resin particle dispersion 2.
[0391] <Production Example of Toner Granules 1>
[0392] The toner granules 1 are produced by the following steps: The following materials are placed in a mill (Mitsui MiikeMachinery Co., Ltd.) and further dispersed at 220 rpm for 5 hours using zirconia granules with a diameter of 1.7 mm to obtain pigment masterbatch.
[0393] -60.0 parts of styrene
[0394] - 7 parts carbon black (manufactured by Orion Engineered Carbons GmbH, trade name "Printex 35")
[0395] - Charge control agent (manufactured by Orient Chemical Industries, Ltd.: Bontron E-89) 0.10 parts
[0396] A total of 450 parts of 0.1 mol / L Na3PO4 aqueous solution were added to 720 parts of ion-exchanged water, then heated to 60°C, and then 67.7 parts of 1.0 mol / L CaCl2 aqueous solution were added to obtain an aqueous medium including a dispersion stabilizer.
[0397] (Preparation of polymeric monomer compositions)
[0398]
[0399] The above materials were uniformly dispersed and mixed using a grinder (manufactured by Mitsui Miike Machinery Co., Ltd.). The mixture was then heated to 60°C, and 10.0 parts of paraffin wax (HNP-51, manufactured by Nippon Seiro Co., Ltd.) as a hydrocarbon wax were added, mixed, and dissolved to obtain a polymerizable monomer composition.
[0400] The polymerizable monomer composition was placed in an aqueous medium and stirred and granulated at 12,000 rpm for 10 minutes at 60°C under a N2 atmosphere in a TK homogenizer (manufactured by Tokushu Kagaku Kogyo Co., Ltd.). Then, while stirring with a paddle stirrer, 8.0 parts of tert-butyl peroxypentanoate were added as a polymerization initiator, the temperature was raised to 74°C, and the reaction was carried out for 3 hours. After the reaction was completed, the suspension was heated to 100°C and maintained at pH (1) 5.0 for 2 hours as the high-temperature, high-pH treatment step described above. Then, while maintaining the suspension at 100°C, 0.9 mol / L Na2CO3 aqueous solution was added to adjust the pH (2) of the suspension to 8.0, and the suspension was maintained for 30 minutes. Then, the suspension was cooled to 25°C by natural cooling at room temperature. Then, hydrochloric acid was added to the suspension for thorough washing to dissolve the dispersion stabilizer. Then, toner particles with a weight-average particle size of 7.1 μm were obtained by filtration and drying.
[0401] <Production examples of colorant granules 2 to 7, 10 and 11>
[0402] Except for changing the type of polyester resin, the amount of polyester resin, and the high temperature and high pH treatment conditions as shown in Table 3, toner particles 2 to 7, 10 and 11 are obtained by performing the same operations as in the production example of toner particles 1.
[0403] [Table 3]
[0404]
[0405] <Production Example of Toner Granules 8>
[0406] (Preparation of styrene-acrylic resin particle dispersion)
[0407] -77 parts styrene
[0408] - 23 parts n-butyl acrylate
[0409] A solution prepared by dissolving 1.0 part of anionic surfactant (Dowfax, manufactured by Dow Chemical Co., Ltd.) in 60 parts of ion-exchanged water was added to a solution obtained by mixing the above materials, and the components were dispersed and emulsified in a flask to produce a monomer emulsion. Subsequently, 2.0 parts of anionic surfactant (Dowfax, manufactured by Dow Chemical Co., Ltd.) were dissolved in 90 parts of ion-exchanged water, 2.0 parts of the monomer emulsion were added thereto, and then 10 parts of ion-exchanged water in which 1.0 part of ammonium persulfate was dissolved were further added.
[0410] Subsequently, the remaining monomer emulsion was added within 3 hours, and the inside of the flask was purged with nitrogen. The solution in the flask was then heated to 65°C in an oil bath while stirring, and emulsification polymerization continued for 5 hours under the same conditions to obtain a styrene-acrylic resin particle dispersion. The solid content in the styrene-acrylic resin particle dispersion was adjusted to 20% by mass by adding ion-exchanged water.
[0411] (Preparation of colorant particle dispersion)
[0412] - Cyan pigment (manufactured by Dainichiseika Color & Chemicals Mfg. Co., Ltd., Pigment Blue 15:3 (copper phthalocyanine)) 45 parts
[0413] - Anionic surfactant (Neogen R, manufactured by DKS Co., Ltd.) 2 parts
[0414] - 250 portions of ion-exchanged water
[0415] The above materials were mixed, dissolved, and dispersed for approximately 1 hour using a high-pressure impact disperser (ULTIMIZER, manufactured by Sugino Machine Ltd., HJP30006) to obtain a colorant particle dispersion. The volume average particle size (D50v) of the particles in the colorant particle dispersion was 150 nm. Then, ion-exchanged water was added to obtain a solid content concentration of 20% by mass.
[0416] (Preparation of release agent particle dispersion)
[0417] - Paraffin wax (hydrocarbon wax, HNP9, manufactured by Nippon Seiro Co., Ltd., melting temperature 75°C, second endothermic peak temperature (one second endothermic peak) 84°C) 270 parts
[0418] - Anionic surfactant (Neogen RK, manufactured by DKS Co., Ltd.) 13.5 parts
[0419] (Active ingredient 60% by mass, relative to 3% by mass of release agent)
[0420] - 21.6 parts of ion-exchanged water
[0421] The above materials were mixed and the release agent dissolved using a pressure-discharge homogenizer (Gaulin homogenizer, manufactured by Gaulin Co.) at an internal liquid temperature of 120°C. The mixture was then dispersed at a dispersion pressure of 5 MPa for 120 minutes, followed by dispersion at 40 MPa for 360 minutes, and then cooled to obtain a dispersion. Ion-exchanged water was added to adjust the solid content to 20% by mass, and this was used as the release agent particle dispersion.
[0422] (Production of colorant granules)
[0423]
[0424] The above materials were placed as nucleation materials in a 3-liter reaction vessel equipped with a thermometer, pH meter and stirrer. 1.0% nitric acid was added at 25°C to adjust the pH to 3.0. Then, while dispersing with a homogenizer (ULTRA-TURRAX T50 manufactured by IKA) at 5000 rpm, 100 parts of a 2.0% by mass magnesium chloride aqueous solution were added as flocculants and dispersed for 6 minutes.
[0425] Subsequently, the mixture was heated to 53°C in a water bath while stirring with a stirring blade and adjusting the rotation speed. The volume average particle size of the formed aggregates was appropriately confirmed using a Coulter Multisizer III, and when the volume average particle size reached 5.0 μm, the temperature was maintained, and 205 parts of polyester resin particle dispersion 1 were added as a shell-forming material over 5 minutes. Then, after maintaining at 50°C for 30 minutes, the temperature was increased to 90°C while adjusting the pH to 9.0, and then maintained at 90°C.
[0426] Subsequently, hydrochloric acid was added to adjust the pH (1) to 5.0 at 90°C, followed by further stirring for 30 minutes. Then, a 0.9 mol / L Na₂CO₃ aqueous solution was added, and the pH (2) was adjusted to 5.5, which was then maintained for 30 minutes. The mixture was then cooled to 25°C, filtered, and subjected to solid-liquid separation, followed by washing with deionized water. After washing, toner particles with a weight-average particle size of 7.2 μm were obtained by using a vacuum dryer.
[0427] <Production Example of Toner Granules 9>
[0428] The following materials were thoroughly mixed using an FM mixer (manufactured by Nippon Coke Industries Co., Ltd.) and then melt-mixed using a twin-screw mixer (manufactured by Ikegai Iron Works Co., Ltd.) with the temperature set at 100°C.
[0429] -Styrene-acrylic resin 1 95.0 parts
[0430] -HNP9 (melting point: 76°C, manufactured by Nippon Seiro Co., Ltd.) 5.0 parts
[0431] -CI Pigment Blue 15:3 6.0 parts
[0432] The obtained compound was cooled and coarsely ground to below 1 mm using a hammer mill to obtain coarse powder. Next, the obtained coarse powder was transformed into fine powder with a size of about 5 μm using a turbomill manufactured by Turbo Industries, Ltd., and then the fine powder and coarse powder were further separated using a multi-stage classifier utilizing the wall effect to obtain toner base particles 1.
[0433] A total of 450 parts of 0.1 mol / L Na3PO4 aqueous solution were added to 720 parts of ion-exchanged water, and then heated to 60 °C in a N2 atmosphere. Then, 67.7 parts of 1.0 mol / L CaCl2 aqueous solution were added to obtain an aqueous medium including a dispersion stabilizer.
[0434] A total of 200.0 parts of toner base particles 1 were placed in an aqueous medium and dispersed for 30 minutes at 7000 rpm using a TK homogenizer at 40°C. Ion-exchanged water was added to adjust the concentration of toner base particles in the dispersion to 20.0% by mass to obtain toner base particle dispersion 1.
[0435] Weigh the following sample into the reaction vessel and mix it using the propeller blades.
[0436] - Toner base particle dispersion 1,500.0 parts
[0437] - Polyester resin particle dispersion 1 20.0 parts
[0438] Next, the pH of the obtained mixture was adjusted to 7.0 using a 1 mol / L NaOH aqueous solution, and the temperature of the mixture was adjusted to 30°C. The mixture was then stirred at 200 rpm using a propeller agitator and held for 1.0 hour. Then, the temperature was increased to 80°C at a rate of 1°C / min while stirring with a propeller agitator and held for 2 hours. Subsequently, as part of the above high-temperature, high-pH treatment step, the temperature of the suspension was increased to 90°C while stirring the obtained dispersion with a propeller agitator, and hydrochloric acid was added to adjust the pH (1) of the suspension to 5.0, held for 30 minutes. Then, a 0.9 mol / L Na₂CO₃ aqueous solution was added at the suspension temperature of 90°C, and the pH (2) of the suspension was adjusted to 5.5, held for 30 minutes. The suspension was then cooled to 25°C by natural cooling at room temperature. Hydrochloric acid was then added to the suspension for thorough washing to dissolve the dispersion stabilizer. Finally, toner particles 9 with a weight-average particle size of 7.1 μm were obtained by filtration and drying.
[0439] <Production Example of Toner Granules 12>
[0440] (Preparation of aqueous media)
[0441] A total of 14.7 parts magnesium chloride was dissolved in a reaction vessel containing 350.0 parts ion-exchanged water and then maintained at 65°C for 1.0 hour while purging with nitrogen. The mixture was stirred at 12,000 rpm using a TK homogenizer (manufactured by Tokushu KagakuKogyo Co., Ltd.). While maintaining stirring, an aqueous solution of sodium hydroxide, prepared by dissolving 10.4 parts sodium hydroxide in 50.0 parts ion-exchanged water, was simultaneously added to the reaction vessel to prepare an aqueous medium including a dispersion stabilizer. Then, 1.0 mol / L hydrochloric acid was added to the aqueous medium in the reaction vessel to adjust the pH to 5.0 and prepare the aqueous medium.
[0442] (Preparation of polymeric monomer compositions)
[0443] Except for changing the polyester resin 1 of the polymerizable monomer composition of the toner particles 1 to polyester resin 4, the polymerizable monomer composition is obtained by operating in the same manner.
[0444] (Granulation step)
[0445] While maintaining the temperature of the aqueous medium at 70°C and the stirring speed at 12,000 rpm, the polymerizable monomer composition was placed in the aqueous medium, and 7.0 parts of tert-butyl peroxypentanoate were added as a polymerization initiator. Granulation was carried out for 10 minutes while maintaining the stirring speed at 12,000 rpm.
[0446] (Aggregation Step)
[0447] The high-speed stirrer was replaced with a stirrer equipped with propeller blades, and the reaction was carried out at 80°C for 3 hours while stirring at 150 rpm. After the reaction was complete, the suspension was heated to 100°C and maintained at pH (1) 5.0 for 2 hours as the high-temperature, high-pH treatment step described above. Then, while maintaining the suspension at 100°C, a 0.9 mol / L Na₂CO₃ aqueous solution was added to adjust the pH (2) of the suspension to 5.5, and the suspension was maintained for 30 minutes. Then, the suspension was cooled to 25°C by natural cooling at room temperature. Then, hydrochloric acid was added to the suspension for thorough washing to dissolve the dispersion stabilizer. Then, toner particles 12 with a weight average particle size of 7.4 μm were obtained by filtration and drying.
[0448] <Production Example of Toner Granules 13>
[0449] (Addition of ammonium compounds)
[0450] As an ammonium compound, a 10% (w / w) ammonia solution was used. A total of 2.5 parts of the ammonium compound were added to 1000 parts of polyester resin particle dispersion 2, and then stirred for 3 minutes.
[0451] (Preparation of toner component dispersion)
[0452] After adding the ammonium compound, the following components are placed in a stirring tank equipped with a thermometer, pH meter, stirrer, and jacket, and then stirred for 10 minutes. The colorant particle dispersion and the release agent particle dispersion are obtained by performing the same operations as described in the production example of colorant particles 8 for the preparation of colorant particle dispersion and release agent particle dispersion.
[0453]
[0454] While gradually adding 125 parts of an aqueous aluminum sulfate solution to the dispersion mixture placed in the stirred tank, the mixture was introduced into a Cavitron CD1010 (manufactured by Eurotech Co., Ltd.) through the bottom valve of the stirred tank and dispersed for 10 minutes. After the addition was complete, the jacket temperature was raised to 50°C, and after 120 minutes, the particle size was measured using a Multisizer II (pore size: 50 μm, manufactured by Beckman-Coulter Inc.). The volume average particle size was 5.0 μm. Then, 312 parts of an additional polyester resin particle dispersion 1 were added, and then maintained for 30 minutes.
[0455] Subsequently, a 4% (w / w) sodium hydroxide aqueous solution was added to the stirred tank to adjust the pH to 9.0, and the jacket temperature was then raised to 90°C and maintained. Agglomeration of the particles was confirmed at 4 hours by observing the shape and surface properties of the aggregated particles every 30 minutes using an optical microscope and a scanning electron microscope (FE SEM), and the resulting slurry was cooled to 40°C. The cooled slurry was sieved using a vibrating screen (KGC800, manufactured by Kowa Kogyosho Co., Ltd.) with a 15 μm opening, and then filtered using a filter press (manufactured by Tokyo Engineering Co., Ltd.). Then, 10 times the amount of ion-exchanged water was passed through the filter press to wash the ion-exchanged particles. The washed toner particles were dried using a circulating airflow dryer (Flash Jet Dryer FJD-2 manufactured by Seishin Enterprise Co., Ltd.) via cyclone collection to obtain toner particles 13 with a weight-average particle size of 7.5 μm.
[0456] <Production Example of Toner 1>
[0457] The following external additives were added to 100 parts of toner granules 1, and the mixture was stirred for 10 minutes at a circumferential speed of 32 m / s using an FM mixer (manufactured by Nippon Coke Co., Ltd.). Coarse particles were removed using a sieve with an opening of 45 μm to obtain toner 1. Table 5 shows the physical properties of the obtained toner 1.
[0458] - 1.0 part of fine silica particles
[0459] <Production Examples of Toners 2 to 26>
[0460] Except for changing the type of toner particles, silica fine particles, and the number of silica fine particles added in the production example of toner 1 as shown in Table 4, toners 2 to 26 are produced by performing the same operations as in the production example of toner 1.
[0461] [Table 4]
[0462]
[0463] [Table 5]
[0464]
[0465] Toners 1 to 18 and 20 to 26 each have more than one peak of the standard value. Toner 19 has no peak of the standard value.
[0466] (Examples 1 to 17, Comparative Examples 1 to 9)
[0467] The following evaluations were conducted using toners 1 to 26. The evaluation results are shown in Table 6. The evaluation methods and criteria are described below.
[0468] A modified LBP-712Ci (manufactured by Canon Inc.), a commercially available laser printer, was used as the image forming device. The printer was modified by setting the processing speed to 250 mm / s. A commercially available toner cartridge 040H (cyan) (manufactured by Canon Inc.) was used as the processing cartridge. Product toner was removed from the cartridge, and the cartridge was cleaned by blowing air and then filled with 240g of toner to be evaluated. Product toner was removed from each of the yellow, magenta, and black stations and inserted into the yellow, magenta, and black cartridges, which have a non-operating toner residue detection mechanism, for evaluation.
[0469] <Stability Testing in Harsh Environments>
[0470] A total of 240g of the obtained toners 1 to 26 were each filled into a toner container and placed in a low-temperature, low-humidity environment (15°C, 10% RH) for 24 hours, and then the environment was changed to a high-temperature, high-humidity environment (55°C, 95% RH) within 24 hours. The toners were then placed in a high-temperature, high-humidity environment for 24 hours, and then the environment was changed to a low-temperature, low-humidity environment (15°C, 10% RH) again within 24 hours. The toners that had undergone the above operation for three cycles were removed. The time graph of the thermal cycling is shown in... Figure 1 middle.
[0471] To evaluate the image appearance of the toner after being placed under the aforementioned harsh conditions, the cartridge was placed in a high-temperature and high-humidity environment (32.0°C, 80% RH) for one day, and then image density, fogging, and vertical stripes on halftone images were evaluated under the same conditions. In the high-temperature and high-humidity environment, the toner's fluidity may decrease, image density may decrease due to toner aggregation, and fogging and vertical stripes on halftone images may occur; therefore, the evaluation was conducted under more stringent conditions.
[0472] As part of the image density test, a solid black image was output with a 5mm front margin and 5mm left and right margins. Image density was measured using a Macbeth density meter (manufactured by Macbeth Co.) as a reflectance density meter and an SPI color filter. Image density was measured at nine points in the solid black image, and the average value was evaluated as the image density. The criteria for determining image density are as follows. The evaluation results are shown in Table 6. A value of C or higher is considered good.
[0473] (Evaluation criteria for image density)
[0474] A: Image density is above 1.40.
[0475] B: Image density is above 1.30 and below 1.40.
[0476] C: Image density is above 1.20 and below 1.30
[0477] D: Image density less than 1.20
[0478] As a fogging test, a solid white image was output, and its reflectance was measured using a REFLECTOMETER MODEL TC-6DS manufactured by Tokyo Denshoku Co., Ltd. Simultaneously, the reflectance of the transfer paper (standard paper) before the solid white image was formed was measured in the same manner. A green color filter was used as the color filter. Fogging was calculated from the reflectance before and after the solid white image output using the following formula.
[0479] Fogging (reflectance) (%) = Reflectance of standard paper (%) - Reflectance of white image sample (%)
[0480] The criteria for determining fogging are as follows. The evaluation results are shown in Table 6. A score of C or above is considered good.
[0481] (Evaluation criteria for fogging)
[0482] A: Fogging (reflectivity) is less than 1.0%.
[0483] B: Fogging (reflectivity) is above 1.0% and below 2.0%.
[0484] C: Fogging (reflectivity) is above 2.0% and below 3.0%.
[0485] D: Fogging (reflectivity) is above 3.0%.
[0486] As an evaluation of vertical stripes on a halftone image, a halftone image is output, and the presence or absence of vertical stripes, known as development stripes caused by toner aggregates, is visually confirmed. The criteria for determining vertical stripes on a halftone image are as follows. The evaluation results are shown in Table 6. A score of C or higher is considered good.
[0487] (Evaluation criteria for vertical stripes in halftone images)
[0488] A: I can't see the vertical stripes.
[0489] B: More than three thin stripes can be seen.
[0490] C: You can see 4 to 10 fine stripes.
[0491] D: More than 11 fine stripes can be seen.
[0492] <Durability evaluation after storage stability testing in harsh environments>
[0493] Following a harsh environment storage stability test, the cartridges were subjected to an image output test for four days in a high temperature and humidity environment (32.0°C, 80% RH) with a setting that printed two horizontal lines at a 4% print rate as one job, producing 2500 prints per day, for a total of 10000 prints. The printer was paused between jobs, and then the next job began. Image density, fogging, and vertical stripes on halftone images were then evaluated. The evaluation methods and criteria for image density, fogging, and vertical stripes on halftone images were the same as those used in the harsh environment storage stability test. The evaluation results are shown in Table 6.
[0494] [Table 6]
[0495]
[0496] Although the invention has been described with reference to exemplary embodiments, it should be understood that the invention is not limited to the disclosed exemplary embodiments. The scope of the appended claims should be interpreted in the broadest sense to cover all such modifications and equivalent structures and functions.
Claims
1. A toner, characterized in that, It includes: Colorant particles containing binder resins and hydrocarbon waxes; and Inorganic fine particles, among which The toner comprises silica fine particles surface-treated with polydimethylsiloxane represented by formula (A) and polydimethylsiloxane represented by formula (B) as the inorganic fine particles; The adhesive resin comprises polyester resin; The toner particles include core particles and shells on the surface of the core particles; The core particles comprise a styrene-acrylic resin; The shell is composed of the polyester resin; In the analysis of the volatile organic components of the silica fine particles by headspace analysis at a heating temperature of 150°C, the total amount of trimethylsilanol, converted to octamethyltrisiloxane, based on the mass of the silica fine particles, is 1.0 to 5.0 ppm. In the measurement of the toner particles from their surface to a depth of 100 nm using time-of-flight secondary ion mass spectrometry, when the value obtained by dividing the amount of ions represented by the structure below (C) by the total number of counted ions is used as the standard value, One or more peaks of the standard value exist within a range of 100 nm from the surface of the toner particles; When the maximum value among more than one peak of the standard value is represented by A(dmax), and the standard value on the surface of the toner particles is represented by A(0), The A(dmax) and the A(0) satisfy the following equations (1) and (2): 1.05≤A(dmax) / A(0)≤5.00(1) A(0)≥0.010 (2) In equation (B), R 1 It can be a methanol group, hydroxyl group, epoxy group, carboxyl group, alkyl group, or hydrogen atom, and R 2 The group is a methanol group, a hydroxyl group, an epoxy group, a carboxyl group, or a hydrogen atom; n and m are the average number of repeating units, n is 30 to 200, and m is 30 to 200; and each methyl group -CH3 in the side chain of formula (B) can be replaced by a methanol group, a hydroxyl group, an epoxy group, a carboxyl group, or a hydrogen atom.
2. The toner according to claim 1, wherein the polydimethylsiloxane represented by formula (B) is a polydimethylsiloxane represented by formula (D). In equation (D), p is the average number of repeating units, which ranges from 30 to 200.
3. The toner according to claim 1 or 2, wherein the number-average particle size of the primary particles of the silica fine particles is 5 to 30 nm.
4. The toner according to claim 1 or 2, wherein When, in the analysis by time-of-flight secondary ion mass spectrometry, the standard value at a depth of 100 nm from the surface of the toner particle is represented by A(100), The values of A(dmax) and A(100) satisfy the following equation (3). 1.05≤A(dmax) / A(100)≤5.00(3).
5. The toner according to claim 1 or 2, wherein... The polyester resin comprises monomer units represented by formula (E), monomer units represented by formula (F), and monomer units represented by formula (G); The content ratio of the monomer unit represented by the following formula (E) in the polyester resin is 30% to 50% by mass. The content ratio of the monomer units represented by the following formula (F) in the polyester resin is 25% to 50% by mass; and The content ratio of the monomer units represented by the following formula (G) in the polyester resin is 0.4 to 50% by mass: in, In equation (E), R 3 Representing a benzene ring, in formula (F), R 4 Each represents ethylidene or propylidene, x and y are each integers greater than or equal to 1, and the average value of x+y is between 2 and 10. In formula (G), R 5 It indicates ethylene or propylene.
6. The toner according to claim 1 or 2, wherein... The adhesive resin comprises polyester resin, and The polyester resin comprises monomer units represented by the following formula (H). 。 7. The colorant according to claim 6, wherein the content ratio of the monomer unit represented by formula (H) in the polyester resin is 1.0 to 4.0 by mass.
8. The toner according to claim 1 or 2, wherein, In cross-sectional observations of the toner using a transmission electron microscope, the average thickness of the shell was 100 to 200 nm.
9. A toner, characterized in that, It includes: Colorant particles containing styrene-acrylic resins, polyester resins, and hydrocarbon waxes; and Inorganic fine particles, among which The inorganic fine particles comprise silica fine particles surface-treated with polydimethylsiloxane represented by formula (A) and polydimethylsiloxane represented by formula (B); The toner particles include core particles and shells on the surface of the core particles; The core particles comprise the styrene-acrylic resin; The shell is composed of the polyester resin; In cross-sectional observation of the toner using a transmission electron microscope, the average thickness of the shell was 100 to 200 nm. In the measurement of the toner particles from their surface to a depth of 100 nm using time-of-flight secondary ion mass spectrometry, when the value obtained by dividing the amount of ions represented by the structure below (C) by the total number of counted ions is used as the standard value, One or more peaks of the standard value exist within a range of 100 nm from the surface of the toner particles; When the maximum value among more than one peak of the standard value is represented by A(dmax), and the standard value on the surface of the toner particles is represented by A(0), The A(dmax) and the A(0) satisfy the following equations (1) and (2): 1.05≤A(dmax) / A(0)≤5.00(1) A(0)≥0.010 (2) In equation (B), R 1 It can be a methanol group, hydroxyl group, epoxy group, carboxyl group, alkyl group, or hydrogen atom, and R 2 The group is a methanol group, a hydroxyl group, an epoxy group, a carboxyl group, or a hydrogen atom; n and m are the average number of repeating units, n is 30 to 200, and m is 30 to 200; and each methyl group (-CH3) in the side chain of formula (B) can be replaced by a methanol group, a hydroxyl group, an epoxy group, a carboxyl group, or a hydrogen atom.
10. The toner according to claim 9, wherein the amount of surface treatment of the polydimethylsiloxane represented by formula (A) is 3 to 40 parts by weight relative to 100 parts by weight of the silica fine particles before surface treatment, and In the surface treatment, the mass ratio (B) / (A) of the polydimethylsiloxane represented by formula (B) to the polydimethylsiloxane represented by formula (A) is from 0.05 to 10.00.
Citation Information
Patent Citations
toner
JP2009157161A
Toner and method for manufacturing the toner
JP2017044981A
Positively chargeable toner
CN109696807A
Toner
CN111948921A
